Copper-clad laminates, wiring boards, and resin-coated copper foils
Patent Information
- Application Number
- JP2021554348
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-10-25
- Filing Date
- 2020-10-15
- Publication Date
- 2025-03-03
- Estimated Expiration
- 2040-10-15
Smart Images

Figure 0007637902000029 
Figure 0007637902000030 
Figure 0007637902000031
Abstract
Description
[Technical field]
[0001] The present invention relates to a copper-clad laminate, a wiring board, and a resin-coated copper foil. [Background technology]
[0002] With the increase in the amount of information processed by various electronic devices, mounting technologies such as higher integration of mounted semiconductor devices, higher density wiring, and multi-layering are rapidly advancing. In addition, wiring boards used in various electronic devices are required to be compatible with high frequencies, such as millimeter wave radar boards for in-vehicle use.
[0003] When a signal is transmitted to the wiring provided on the wiring board, transmission loss due to the conductor forming the wiring and transmission loss due to the inductor around the wiring occur. It is known that these transmission losses are particularly likely to occur when a high-frequency signal is transmitted to the wiring provided on the wiring board. For this reason, in order to increase the signal transmission speed, the wiring board is required to reduce the loss during signal transmission. This is particularly required for wiring boards that support high frequencies. In order to meet this requirement, it is considered to use a material with a low dielectric constant and dielectric loss tangent as a substrate material for manufacturing an insulating layer that constitutes the wiring board. Examples of such substrate materials include resin compositions containing polyphenylene ether. Examples of metal-clad laminates obtained by using such materials with low dielectric constants and dielectric loss tangents as substrate materials include, for example, the metal-clad laminates described in Patent Document 1.
[0004] Patent Document 1 describes a metal-clad laminate comprising a cured insulating layer containing a polyphenylene ether compound, a metal layer bonded to the insulating layer, and an intermediate layer containing a silane compound interposed between the insulating layer and the metal layer, the metal layer having a bonding surface bonded to the insulating layer via the intermediate layer, and the ten-point average roughness Rz of the bonding surface being 0.5 μm or more and 4 μm or less. Patent Document 1 discloses that a metal-clad laminate capable of manufacturing a printed wiring board with reduced loss during signal transmission can be obtained.
[0005] As described above, wiring boards such as printed wiring boards are required to have higher signal transmission speeds in order to handle high frequencies. In addition, wiring boards used in various electronic devices are required to be less susceptible to changes in the external environment. For example, high heat resistance is required so that delamination does not occur when heated. In order to meet these requirements, various copper-clad laminates, wiring boards, and resin-coated copper foils have been studied. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2016-28885 A Summary of the Invention
[0007] The present invention has been made in view of the above circumstances, and aims to provide a copper-clad laminate and a resin-coated copper foil that can be used to suitably manufacture a wiring board having a high signal transmission speed and high heat resistance. Another aim of the present invention is to provide a wiring board having a high signal transmission speed and high heat resistance.
[0008] One aspect of the present invention is a copper-clad laminate comprising an insulating layer and a copper foil in contact with at least one surface of the insulating layer, wherein the insulating layer comprises a cured product of a resin composition containing a polymer having a structural unit represented by the following formula (1) in its molecule, and the copper-clad laminate is etched with a copper chloride solution to expose the insulating layer, and the amount of chromium element on an exposed surface thereof measured by X-ray photoelectron spectroscopy is 7.5 atomic % or less relative to the total amount of elements measured by X-ray photoelectron spectroscopy, and the surface roughness of the exposed surface is 2.0 μm or less in ten-point average roughness.
[0009] [ka] In formula (1), Z represents an arylene group, R1 to R3 each independently represent a hydrogen atom or an alkyl group, and R4 to R6 each independently represent a hydrogen atom or an alkyl group having 1 to 6 carbon atoms.
[0010] Another aspect of the present invention is a resin-coated copper foil comprising a resin layer and a copper foil in contact with at least one surface of the resin layer, the resin layer comprising a resin composition containing a polymer having a structural unit represented by formula (1) in the molecule, or a semi-cured product of the resin composition, the resin layer of the resin-coated copper foil being cured, the copper foil in contact with the surface of the cured resin layer being etched with a copper chloride solution to expose the cured resin layer, the amount of chromium element measured by X-ray photoelectron spectroscopy being 7.5 atomic % or less relative to the total amount of elements measured by X-ray photoelectron spectroscopy, and the surface roughness of the exposed surface being 2.0 μm or less in ten-point average roughness. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of a copper-clad laminate according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing an example of a prepreg according to an embodiment of the present invention. [Diagram 3] FIG. 3 is a schematic cross-sectional view showing an example of a wiring board according to an embodiment of the present invention. [Figure 4] FIG. 4 is a schematic cross-sectional view showing another example of a wiring board according to an embodiment of the present invention. [Diagram 5] FIG. 5 is a schematic cross-sectional view showing an example of a resin-coated copper foil according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] In a wiring board obtained by forming wiring by partially removing the copper foil provided on a copper-clad laminate, even if another insulating layer is formed on the surface of the insulating layer exposed by the wiring formation, no wiring made of copper foil exists between these insulating layers. For this reason, it was thought that the copper foil provided on the copper-clad laminate used to obtain the wiring board would not affect delamination between insulating layers.
[0013] However, according to the study of the present inventors, it was found that the likelihood of delamination between insulating layers varies depending on the copper foil provided in the copper-clad laminate. The present inventors inferred that if there is no conductor derived from the copper foil on the exposed surface, which is the surface of the insulating layer exposed by wiring formation, the exposed surface and other insulating layers are favorably bonded, and the state of the exposed surface does not affect the occurrence of delamination. From this, it was inferred that when the copper foil in the copper-clad laminate is removed by etching, a very small amount of metal components derived from the copper foil may remain on the exposed surface. In addition, it was inferred that the state of the exposed surface is greatly influenced by its surface roughness. As a result of various studies on the influence of the remaining metal components and surface roughness, the present inventors found that the likelihood of delamination between insulating layers varies depending on the amount of chromium elements and surface roughness present on the exposed surface where the insulating layer is exposed by etching the copper-clad laminate with a copper chloride solution.
[0014] After various studies, the inventors found that if the copper-clad laminate is etched with a copper chloride solution to expose the insulating layer, the exposed surface of the copper-clad laminate has a predetermined chromium element content and a predetermined surface roughness, the occurrence of delamination can be suppressed in the wiring board obtained by using the copper-clad laminate. That is, instead of specifying the copper foil removal conditions (etching conditions) and the copper foil composition, the inventors found that if the copper-clad laminate is such that the chromium element content and surface roughness of the exposed surface of the insulating layer exposed by a predetermined etching process are predetermined values, the occurrence of delamination can be suppressed in the wiring board obtained by using the copper-clad laminate. From these findings, the present invention as described below has been conceived.
[0015] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these.
[0016] [Copper-clad laminate] A copper clad laminate according to an embodiment of the present invention comprises an insulating layer and a copper foil in contact with at least one surface of the insulating layer. As shown in FIG. 1, this copper clad laminate 11 may comprise an insulating layer 12 and a copper foil 13 arranged in contact with both surfaces of the insulating layer. The copper clad laminate may also comprise a copper foil in contact with only one surface of the insulating layer. FIG. 1 is a schematic cross-sectional view showing the configuration of a copper clad laminate 11 according to this embodiment.
[0017] The copper-clad laminate 11 has an insulating layer 12 that includes a cured product of a resin composition containing a polymer having a structural unit represented by the following formula (1) in the molecule. The copper-clad laminate 11 has an exposed surface, where the insulating layer 12 is exposed by etching the copper-clad laminate 11 with a copper chloride solution, and the amount of chromium element measured by X-ray photoelectron spectroscopy (XPS) is 7.5 atomic % or less relative to the total amount of elements measured by XPS. The copper-clad laminate 11 has a surface roughness of 2.0 μm or less in ten-point average roughness.
[0018] [ka] In formula (1), Z represents an arylene group, R1 to R3 each independently represent a hydrogen atom or an alkyl group, and R4 to R6 each independently represent a hydrogen atom or an alkyl group having 1 to 6 carbon atoms.
[0019] In such a copper-clad laminate, first, the cured material contained in the insulating layer is a cured material obtained by curing a resin composition containing the polymer, and therefore it is believed that the heat resistance of the insulating layer can be improved.
[0020] As described above, the present inventors have found that when another insulating layer is formed on the surface of an insulating layer present between wirings in a wiring board manufactured from a copper-clad laminate, delamination occurring between the insulating layer between wirings and the other insulating layer is also influenced by the copper foil that was originally present, even if there is no copper foil between them. From this, it is believed that etching residues derived from the copper foil are present on the exposed surface where the insulating layer is exposed by the etching process. The present inventors have inferred that if a compound containing a chromium element is present as this etching residue, delamination is likely to occur when heated. In addition, if the amount of chromium element present on the exposed surface is small as described above, it is believed that the amount of chromium element present on the surface of the insulating layer present between wirings in the wiring board manufactured from the copper-clad laminate, i.e., the amount of compound containing a chromium element, is also small. From this, it is believed that the copper-clad laminate has high heat resistance that can sufficiently suppress delamination even when heated.
[0021] From the above, it is considered that the copper-clad laminate has high heat resistance.
[0022] The cured material contained in the insulating layer is a cured material obtained by curing a resin composition containing the polymer, and therefore has a low dielectric constant and dielectric loss tangent, which is considered to enable the wiring board to reduce transmission loss caused by the dielectric material around the wiring and increase the signal transmission speed.
[0023] In addition, since the surface roughness of the exposed surface is low, it is considered that the smoothness of the contact surface between the copper foil and the insulating layer is also high. From this, it is considered that the wiring board obtained from the copper-clad laminate also has a high smoothness of the contact surface between the wiring and the insulating layer. It is considered that the signal transmitted through the wiring is concentrated near the surface of the conductor constituting the wiring due to the skin effect. It is considered that this effect becomes more prominent as the signal transmitted through the wiring becomes higher in frequency. And, when the contact surface between the wiring and the insulating layer becomes smooth, the signal flowing through the wiring flows near the surface with high smoothness, so the transmission distance is shortened. From this, it is considered that this wiring board can reduce the transmission loss caused by the conductor forming the wiring and can increase the transmission speed of the signal.
[0024] For these reasons, it is believed that this wiring board can reduce transmission loss caused by the conductors that form the wiring, as well as transmission loss caused by the dielectric materials around the wiring, and can increase the signal transmission speed.
[0025] From the above, it is considered that the copper-clad laminate is a copper-clad laminate that can be used to suitably manufacture wiring boards that have a high signal transmission speed and high heat resistance.
[0026] (Resin composition) As described above, the resin composition contains the polymer.
[0027] (Polymer) The polymer is not particularly limited as long as it has a structural unit represented by the formula (1) in the molecule. In addition, the polymer may have a structural unit other than the structural unit represented by the formula (1) as long as it has a structural unit represented by the formula (1) in the molecule. In addition, the polymer may contain a repeating unit in which the structural unit represented by the formula (1) is repeatedly bonded, or may be a polymer in which a repeating unit in which the structural unit represented by the formula (1) is repeatedly bonded and a repeating unit in which a structural unit other than the structural unit represented by the formula (1) is repeatedly bonded are randomly bonded. That is, when it has a structural unit other than the structural unit represented by the formula (1), it may be a block copolymer or a random copolymer.
[0028] The arylene group represented by Z in the formula (1) is not particularly limited. Examples of the arylene group include monocyclic aromatic groups such as phenylene groups, and polycyclic aromatic groups in which the aromatic ring is not monocyclic but is polycyclic aromatic such as naphthalene rings. The arylene group also includes derivatives in which the hydrogen atom bonded to the aromatic ring is replaced with a functional group such as an alkenyl group, an alkynyl group, a formyl group, an alkylcarbonyl group, an alkenylcarbonyl group, or an alkynylcarbonyl group.
[0029] The alkyl group represented by R1 to R3 in the formula (1) is not particularly limited, and is preferably, for example, an alkyl group having 1 to 18 carbon atoms, and more preferably an alkyl group having 1 to 10 carbon atoms. Specific examples include a methyl group, an ethyl group, a propyl group, a hexyl group, and a decyl group.
[0030] The alkyl group having 1 to 6 carbon atoms represented by R4 to R6 in the formula (1) is not particularly limited, and specific examples include a methyl group, an ethyl group, a propyl group, and a hexyl group.
[0031] The polymer preferably contains an aromatic polymer having a structural unit derived from a bifunctional aromatic compound having two carbon-carbon unsaturated double bonds bonded to an aromatic ring as the structural unit represented by the formula (1). The structural unit derived from the bifunctional aromatic compound is a structural unit obtained by polymerizing the bifunctional aromatic compound. In this specification, the aromatic polymer is also referred to as a divinyl aromatic polymer.
[0032] The bifunctional aromatic compound is not particularly limited as long as it is a bifunctional aromatic compound having two carbon-carbon unsaturated double bonds bonded to an aromatic ring. Examples of the bifunctional aromatic compound include m-divinylbenzene, p-divinylbenzene, 1,2-diisopropenylbenzene, 1,3-diisopropenylbenzene, 1,4-diisopropenylbenzene, 1,3-divinylnaphthalene, 1,8-divinylnaphthalene, 1,4-divinylnaphthalene, 1,5-divinylnaphthalene, 2,3-divinylnaphthalene, 2,7-divinylnaphthalene, and 2,6-divinylnaphthalene. , 4,4'-divinylbiphenyl, 4,3'-divinylbiphenyl, 4,2'-divinylbiphenyl, 3,2'-divinylbiphenyl, 3,3'-divinylbiphenyl, 2,2'-divinylbiphenyl, 2,4-divinylbiphenyl, 1,2-divinyl-3,4-dimethylbenzene, 1,3-divinyl-4,5,8-tributylnaphthalene, and 2,2'-divinyl-4-ethyl-4'-propylbiphenyl. These may be used alone or in combination of two or more. Among these, the bifunctional aromatic compound is preferably divinylbenzene such as m-divinylbenzene and p-divinylbenzene, and more preferably p-divinylbenzene.
[0033] The aromatic polymer may have not only the structural unit derived from the bifunctional aromatic compound but also other structural units. Examples of the other structural units include a structural unit derived from a monofunctional aromatic compound having one carbon-carbon unsaturated double bond bonded to an aromatic ring, a structural unit derived from a trifunctional aromatic compound having three carbon-carbon unsaturated double bonds bonded to an aromatic ring, a structural unit derived from an indene, and a structural unit derived from an acenaphthylene. The structural unit derived from the monofunctional aromatic compound is a structural unit obtained by polymerizing the monofunctional aromatic compound. The structural unit derived from the trifunctional aromatic compound is a structural unit obtained by polymerizing the trifunctional aromatic compound. The structural unit derived from the indenes is a structural unit obtained by polymerizing indenes. The structural unit derived from the acenaphthylene is a structural unit obtained by polymerizing acenaphthylene.
[0034] The monofunctional aromatic compound may have one carbon-carbon unsaturated double bond bonded to an aromatic ring, and the aromatic ring may have a group other than the carbon-carbon unsaturated double bond bonded.The monofunctional aromatic compound may, for example, be a monofunctional aromatic compound having one carbon-carbon unsaturated double bond bonded to an aromatic ring and no group other than the carbon-carbon unsaturated double bond bonded, or a monofunctional aromatic compound having one carbon-carbon unsaturated double bond bonded to an aromatic ring and further having an alkyl group such as an ethyl group bonded to the aromatic ring.
[0035] Examples of monofunctional aromatic compounds having one carbon-carbon unsaturated double bond bonded to an aromatic ring and no groups other than the carbon-carbon unsaturated double bond bonded include styrene, 2-vinylbiphenyl, 3-vinylbiphenyl, 4-vinylbiphenyl, 1-vinylnaphthalene, 2-vinylnaphthalene, and α-alkyl-substituted styrenes. Examples of α-alkyl-substituted styrenes include α-methylstyrene, α-ethylstyrene, α-propylstyrene, α-n-butylstyrene, α-isobutylstyrene, α-t-butylstyrene, α-n-pentylstyrene, α-2-methylbutylstyrene, α-3-methylbutyl-2-styrene, α-t-butylstyrene, α-t-butylstyrene, α-n-pentylstyrene, α-2-methylbutylstyrene, α-3-methylbutylstyrene, α-t-pentylstyrene, α-n-hexylstyrene, α-ethylstyrene, α-propylstyrene, α-n-butylstyrene, α-iso ...t-pentylstyrene, α-hexylstyrene, α-ethylstyrene, α-propylstyrene, α-n-butylstyrene, α-isobutylstyrene, α-t-butylstyrene, α-n-pentylstyrene, α-t-pentylstyrene, α-hexylstyrene, α-ethylstyrene, α-propylstyrene, α-n-butylstyrene, α-isobutylstyrene, α-t-butylstyrene, α-n-pentylstyrene, α-t-pentylstyrene, α-hexylstyrene, α-ethylstyrene, α-propyl Examples of such styrenes include styrene, α-2-methylpentylstyrene, α-3-methylpentylstyrene, α-1-methylpentylstyrene, α-2,2-dimethylbutylstyrene, α-2,3-dimethylbutylstyrene, α-2,4-dimethylbutylstyrene, α-3,3-dimethylbutylstyrene, α-3,4-dimethylbutylstyrene, α-4,4-dimethylbutylstyrene, α-2-ethylbutylstyrene, α-1-ethylbutylstyrene, α-cyclohexylstyrene, and α-cyclohexylstyrene. These may be used alone or in combination of two or more.
[0036] Examples of monofunctional aromatic compounds having one carbon-carbon unsaturated double bond bonded to an aromatic ring and further having an alkyl group bonded to the aromatic ring include nuclear alkyl-substituted aromatic compounds and alkoxy-substituted styrenes.
[0037] Examples of the nuclear alkyl-substituted aromatic compounds include ethyl vinyl aromatic compounds in which the alkyl group bonded to the aromatic ring is an ethyl group, nuclear alkyl-substituted styrenes in which an alkyl group is bonded to the styrene as the aromatic ring, and nuclear alkyl-substituted aromatic compounds other than the ethyl vinyl aromatic compounds and the nuclear alkyl-substituted styrenes (other nuclear alkyl-substituted aromatic compounds).
[0038] Examples of the ethylvinyl aromatic compounds include o-ethylvinylbenzene, m-ethylvinylbenzene, p-ethylvinylbenzene, 2-vinyl-2'-ethylbiphenyl, 2-vinyl-3'-ethylbiphenyl, 2-vinyl-4'-ethylbiphenyl, 3-vinyl-2'-ethylbiphenyl, 3-vinyl-3'-ethylbiphenyl, 3-vinyl-4'-ethylbiphenyl, 4-vinyl-2'-ethylbiphenyl, 4-vinyl-3'-ethylbiphenyl, 4-vinyl-4'-ethylbiphenyl, 1-vinyl-2-ethyl Examples of the ethylnaphthalene include naphthalene, 1-vinyl-3-ethylnaphthalene, 1-vinyl-4-ethylnaphthalene, 1-vinyl-5-ethylnaphthalene, 1-vinyl-6-ethylnaphthalene, 1-vinyl-7-ethylnaphthalene, 1-vinyl-8-ethylnaphthalene, 2-vinyl-1-ethylnaphthalene, 2-vinyl-3-ethylnaphthalene, 2-vinyl-4-ethylnaphthalene, 2-vinyl-5-ethylnaphthalene, 2-vinyl-6-ethylnaphthalene, 2-vinyl-7-ethylnaphthalene, and 2-vinyl-8-ethylnaphthalene.
[0039] Examples of the nuclear alkyl-substituted styrenes include m-methylstyrene, p-methylstyrene, m-propylstyrene, p-propylstyrene, mn-butylstyrene, pn-butylstyrene, mt-butylstyrene, pt-butylstyrene, mn-hexylstyrene, pn-hexylstyrene, m-cyclohexylstyrene, and p-cyclohexylstyrene.
[0040] Examples of the other nuclear alkyl-substituted aromatic compounds include 2-vinyl-2'-propylbiphenyl, 2-vinyl-3'-propylbiphenyl, 2-vinyl-4'-propylbiphenyl, 3-vinyl-2'-propylbiphenyl, 3-vinyl-3'-propylbiphenyl, 3-vinyl-4'-propylbiphenyl, 4-vinyl-2'-propylbiphenyl, 4-vinyl-3'-propylbiphenyl, 4-vinyl-4'-propylbiphenyl, 1-vinyl-2-propylnaphthalene, 1-vinyl-3-propylnaphthalene, and Examples of propylnaphthalene include 1-vinyl-4-propylnaphthalene, 1-vinyl-5-propylnaphthalene, 1-vinyl-6-propylnaphthalene, 1-vinyl-7-propylnaphthalene, 1-vinyl-8-propylnaphthalene, 2-vinyl-1-propylnaphthalene, 2-vinyl-3-propylnaphthalene, 2-vinyl-4-propylnaphthalene, 2-vinyl-5-propylnaphthalene, 2-vinyl-6-propylnaphthalene, 2-vinyl-7-propylnaphthalene, and 2-vinyl-8-propylnaphthalene.
[0041] Examples of the alkoxy-substituted styrene include o-ethoxystyrene, m-ethoxystyrene, p-ethoxystyrene, o-propoxystyrene, m-propoxystyrene, p-propoxystyrene, on-butoxystyrene, mn-butoxystyrene, pn-butoxystyrene, o-isobutoxystyrene, m-isobutoxystyrene, p-isobutoxystyrene, ot-butoxystyrene, mt-butoxystyrene, pt-butoxystyrene, on-pentoxystyrene, mn-pentoxystyrene, pn-pentoxystyrene, and α-methyl-o-butoxystyrene. , α-methyl-m-butoxystyrene, α-methyl-p-butoxystyrene, ot-pentoxystyrene, mt-pentoxystyrene, pt-pentoxystyrene, on-hexoxystyrene, mn-hexoxystyrene, pn-hexoxystyrene, α-methyl-o-pentoxystyrene, α-methyl-m-pentoxystyrene, α-methyl-p-pentoxystyrene, o-cyclohexoxystyrene, m-cyclohexoxystyrene, p-cyclohexoxystyrene, o-phenoxystyrene, m-phenoxystyrene, and p-phenoxystyrene.
[0042] The monofunctional aromatic compound may be one of the above-listed compounds or a combination of two or more of them. Among the above-listed compounds, styrene and p-ethylvinylbenzene are preferred as the monofunctional aromatic compound.
[0043] Examples of trifunctional aromatic compounds having three carbon-carbon unsaturated double bonds bonded to an aromatic ring include 1,2,4-trivinylbenzene, 1,3,5-trivinylbenzene, 1,2,4-triisopropenylbenzene, 1,3,5-triisopropenylbenzene, 1,3,5-trivinylnaphthalene, and 3,5,4'-trivinylbiphenyl. The trifunctional aromatic compounds may be used alone or in combination of two or more of the above-listed compounds.
[0044] Examples of the indenes include indene, alkyl-substituted indenes, and alkylcyindenes. Examples of the alkyl-substituted indenes include methylindene, ethylindene, propylindene, butylindene, t-butylindene, sec-butylindene, n-pentylindene, 2-methyl-butylindene, 3-methyl-butylindene, n-hexylindene, 2-methyl-pentylindene, 3-methyl-pentylindene, and 4-methyl-pentylindene. Examples of the alkoxyindenes include methoxyindene, ethoxyindene, propoxyindene, butoxyindene, t-butoxyindene, sec-butoxyindene, n-pentoxyindene, 2-methyl-butoxyindene, 3-methyl-butoxyindene, n-hexoxyindene, 2-methyl-pentoxyindene, 3-methyl-pentoxyindene, 4-methyl-pentoxyindene, etc. As the indenes, the above-exemplified compounds may be used alone or in combination of two or more kinds.
[0045] Examples of the acenaphthylenes include acenaphthylene, alkylacenaphthylenes, halogenated acenaphthylenes, and phenylacenaphthylenes. Examples of the alkylacenaphthylenes include 1-methylacenaphthylene, 3-methylacenaphthylene, 4-methylacenaphthylene, 5-methylacenaphthylene, 1-ethylacenaphthylene, 3-ethylacenaphthylene, 4-ethylacenaphthylene, and 5-ethylacenaphthylene. Examples of the halogenated acenaphthylenes include 1-chloroacenaphthylene, 3-chloroacenaphthylene, 4-chloroacenaphthylene, 5-chloroacenaphthylene, 1-bromoacenaphthylene, 3-bromoacenaphthylene, 4-bromoacenaphthylene, and 5-bromoacenaphthylene. Examples of the phenylacenaphthylenes include 1-phenylacenaphthylene, 3-phenylacenaphthylene, 4-phenylacenaphthylene, 5-phenylacenaphthylene, etc. As the acenaphthylenes, the above-exemplified compounds may be used alone or in combination of two or more kinds.
[0046] When the aromatic polymer has not only the structural unit derived from the bifunctional aromatic compound but also other structural units, it is a copolymer of the structural unit derived from the bifunctional aromatic compound and other structural units such as the structural unit derived from the monofunctional aromatic compound, etc. This copolymer may be a block copolymer or a random copolymer.
[0047] As described above, the polymer is not particularly limited as long as it is a polymer having a structural unit represented by the formula (1) in the molecule. The structural unit represented by the formula (1) preferably includes a structural unit represented by the following formula (2). That is, the polymer is preferably a polymer having a structural unit represented by the following formula (2) in the molecule.
[0048] [ka] In formula (2), R4 to R6 are the same as R4 to R6 in formula (1). Specifically, R4 to R6 each independently represent a hydrogen atom or an alkyl group having 1 to 6 carbon atoms. R7 represents an arylene group having 6 to 12 carbon atoms.
[0049] The arylene group having 6 to 12 carbon atoms in the formula (2) is not particularly limited. Examples of the arylene group include monocyclic aromatic groups such as phenylene groups, and bicyclic aromatic groups in which the aromatic ring is not monocyclic but is bicyclic aromatic such as naphthalene rings. The arylene group also includes derivatives in which a hydrogen atom bonded to the aromatic ring is substituted with a functional group such as an alkenyl group, an alkynyl group, a formyl group, an alkylcarbonyl group, an alkenylcarbonyl group, or an alkynylcarbonyl group.
[0050] The structural unit represented by formula (2) preferably contains a structural unit represented by formula (3) below. That is, in the structural unit represented by formula (2), R7 is preferably a phenylene group. The phenylene group may be any one of o-phenylene group, m-phenylene group, and p-phenylene group, or may be two or more kinds. The phenylene group preferably contains a p-phenylene group.
[0051] [ka] In formula (3), R4 to R6 are the same as R4 to R6 in formula (1). Specifically, R4 to R6 each independently represent a hydrogen atom or an alkyl group having 1 to 6 carbon atoms.
[0052] The polymer preferably includes a polymer further having a structural unit represented by the following formula (4) in the molecule. That is, the polymer preferably includes a structural unit derived from a monofunctional aromatic compound having one carbon-carbon unsaturated double bond bonded to an aromatic ring as the structural unit represented by the following formula (4). Therefore, the polymer is preferably a polymer having a structural unit represented by the above formula (1) and a structural unit represented by the following formula (4) in the molecule. That is, the polymer may have a structural unit other than the structural unit represented by the above formula (1) and the structural unit represented by the following formula (4) (structural units other than (1) and (4)) as long as the polymer has a structural unit represented by the above formula (1) and a structural unit represented by the following formula (4) in the molecule. The polymer may contain structural units other than the structural units (1) and (4), or may be a polymer, a block copolymer, or a random copolymer in which a repeating unit in which a structural unit represented by the formula (1) is repeatedly bonded, a repeating unit in which a structural unit represented by the following formula (4) is repeatedly bonded, and a repeating unit in which a structural unit other than the structural units (1) and (4) is repeatedly bonded are randomly bonded.
[0053] [ka] In formula (4), R8~R 10 are independent of each other. That is, R8 to R 10 may be the same or different groups. 10 R represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms. 11 represents an aryl group.
[0054] In the formula (4), R to R 10 The alkyl group having 1 to 6 carbon atoms represented by R4 to R6 in the formula (4) is not particularly limited, and may be the same as the alkyl group having 1 to 6 carbon atoms represented by R4 to R6 in the formula (1). 10 Specific examples of the alkyl group having 1 to 6 carbon atoms include a methyl group, an ethyl group, a propyl group, and a hexyl group.
[0055] In the above formula (4), R 11 The aryl group represented by is not particularly limited, and may be an unsubstituted aryl group, or an aryl group in which a hydrogen atom bonded to an aromatic ring is substituted with an alkyl group or the like. The unsubstituted aryl group may be a group in which one hydrogen atom is removed from an aromatic hydrocarbon having one aromatic ring, or a group in which one hydrogen atom is removed from an aromatic hydrocarbon having two or more independent aromatic rings (e.g., biphenyl, etc.). Examples of the aryl group in the formula (4) include an unsubstituted aryl group having 6 to 12 carbon atoms, and an arylene group having 6 to 18 carbon atoms in which a hydrogen atom of an aryl group having 6 to 12 carbon atoms is substituted with an alkyl group having 1 to 6 carbon atoms. Examples of the unsubstituted aryl group having 6 to 12 carbon atoms include a phenyl group, a naphthyl group, and a biphenylyl group. The aryl group in the formula (4), that is, R 11 More specifically, the aryl groups include those shown in Tables 1 and 2 below.
[0056] [Table 1]
[0057] [Table 2]
[0058] The weight average molecular weight of the polymer is preferably 1500 to 40000, more preferably 1500 to 35000. If the weight average molecular weight is too low, the heat resistance and the like tend to decrease. If the weight average molecular weight is too high, the moldability and the like tend to decrease. Therefore, if the weight average molecular weight of the resin composition is within the above range, the heat resistance and moldability are excellent. Here, the weight average molecular weight may be measured by a general molecular weight measurement method, and specifically, a value measured using gel permeation chromatography (GPC) and the like can be mentioned.
[0059] In the polymer, when the total of the structural units in the polymer is 100 mol%, the molar content of the structural unit represented by the formula (1) is preferably within the range of the weight average molecular weight, specifically, preferably 2 to 95 mol%, more preferably 8 to 81 mol%. The molar content of the structural unit represented by the formula (2) and the molar content of the structural unit represented by the formula (3) are the same as the molar content of the structural unit represented by the formula (1), specifically, preferably 2 to 95 mol%, more preferably 8 to 81 mol%. In the case where the polymer has the structural unit represented by the formula (1) and the structural unit represented by the formula (4) in the molecule, the molar content of the structural unit represented by the formula (1) is preferably 2 to 95 mol%, more preferably 8 to 81 mol%, and the molar content of the structural unit represented by the formula (4) is preferably 5 to 98 mol%, more preferably 19 to 92 mol%.
[0060] In the polymer, the average number of the structural units represented by the formula (1) is preferably a number within the range of the weight average molecular weight, specifically, preferably 1 to 160, more preferably 3 to 140. The average number of the structural units represented by the formula (2) and the average number of the structural units represented by the formula (3) are the same as the average number of the structural units represented by the formula (1), specifically, preferably 1 to 160, more preferably 3 to 140. In addition, when the polymer has a structural unit represented by the formula (1) and a structural unit represented by the formula (4) in the molecule, the average number of the structural units represented by the formula (1) is preferably 1 to 160, more preferably 3 to 140, and the average number of the structural units represented by the formula (4) is preferably 2 to 350, more preferably 4 to 300.
[0061] A specific example of the polymer is a polymer containing a structural unit represented by the following formula (6) in the molecule and further containing at least one of a structural unit represented by the following formula (5) and a structural unit represented by the following formula (7). This polymer may be a block copolymer or a random copolymer.
[0062] [ka]
[0063] [ka]
[0064] [ka]
[0065] In the polymer containing the structural unit represented by the formula (6) in the molecule and further containing at least one of the structural unit represented by the formula (5) and the structural unit represented by the formula (7), the molar contents of the structural unit represented by the formula (5), the structural unit represented by the formula (6), and the structural unit represented by the formula (7) are preferably 0 to 92 mol%, 8 to 54 mol%, and 0 to 89 mol%, respectively. The average number of the structural units represented by the formula (5) is preferably 0 to 350, the average number of the structural units represented by the formula (6) is preferably 1 to 160, and the average number of the structural units represented by the formula (7) is preferably 0 to 270.
[0066] The equivalent of the vinyl group contained in the structural unit of the polymer represented by the formula (1) in which R1 to R3 are hydrogen atoms is preferably 250 to 1200, more preferably 300 to 1100. If the equivalent is too small, the vinyl group becomes too many, and the reactivity becomes too high, which may cause problems such as a decrease in the storage stability of the resin composition or a decrease in the flowability of the resin composition. If a resin composition having a too small equivalent is used, there may be a molding problem such as a molding defect such as the generation of voids during multilayer molding due to insufficient flowability, making it difficult to obtain a highly reliable wiring board. In addition, if the equivalent is too large, the vinyl group becomes too few, and the heat resistance of the cured product tends to be insufficient. Therefore, when the equivalent is within the above range, the heat resistance and moldability are excellent. The equivalent of the vinyl group contained in the structural unit represented by the formula (1) in which R1 to R3 are hydrogen atoms is the so-called vinyl equivalent.
[0067] The method for producing the polymer is not particularly limited as long as the polymer can be produced. For example, when the polymer has structural units represented by the formulas (5) to (7) in the molecule, the method for producing the polymer includes a method of reacting divinylbenzene, ethylvinylbenzene, and styrene. In this reaction, a solvent may be n-propyl acetate. In addition, a catalyst may be used in this reaction, and an example of the catalyst may be boron trifluoride diethyl ether complex.
[0068] (hardening agent) The resin composition may contain a curing agent. The resin composition may not contain a curing agent, but in the case of a resin composition containing the polymer, it is preferable to contain a curing agent in order to suitably cure the polymer. The curing agent is not particularly limited as long as it can cure the resin composition containing the polymer. The curing agent may be a curing agent having at least one functional group in the molecule that contributes to the reaction with the polymer. Examples of the curing agent include styrene, styrene derivatives, compounds having an acryloyl group in the molecule, compounds having a methacryloyl group in the molecule, compounds having a vinyl group in the molecule, compounds having an allyl group in the molecule, compounds having an acenaphthylene structure in the molecule, compounds having a maleimide group in the molecule, and compounds having an isocyanurate group in the molecule.
[0069] Examples of the styrene derivatives include bromostyrene and dibromostyrene.
[0070] The compound having an acryloyl group in the molecule is an acrylate compound. The acrylate compound includes a monofunctional acrylate compound having one acryloyl group in the molecule, and a polyfunctional acrylate compound having two or more acryloyl groups in the molecule. The monofunctional acrylate compound includes, for example, methyl acrylate, ethyl acrylate, propyl acrylate, and butyl acrylate. The polyfunctional acrylate compound includes, for example, a diacrylate compound such as tricyclodecane dimethanol diacrylate.
[0071] The compound having a methacryloyl group in the molecule is a methacrylate compound. The methacrylate compound may be a monofunctional methacrylate compound having one methacryloyl group in the molecule, or a polyfunctional methacrylate compound having two or more methacryloyl groups in the molecule. The monofunctional methacrylate compound may be, for example, methyl methacrylate, ethyl methacrylate, propyl methacrylate, and butyl methacrylate. The polyfunctional methacrylate compound may be, for example, a dimethacrylate compound such as tricyclodecane dimethanol dimethacrylate (DCP).
[0072] The compound having a vinyl group in the molecule is a vinyl compound. The vinyl compound includes a monofunctional vinyl compound (monovinyl compound) having one vinyl group in the molecule, and a polyfunctional vinyl compound having two or more vinyl groups in the molecule. The polyfunctional vinyl compound includes, for example, divinylbenzene and polybutadiene.
[0073] The compound having an allyl group in the molecule is an allyl compound. The allyl compound includes a monofunctional allyl compound having one allyl group in the molecule, and a polyfunctional allyl compound having two or more allyl groups in the molecule. The polyfunctional allyl compound includes, for example, a triallyl isocyanurate compound such as triallyl isocyanurate (TAIC), a diallyl bisphenol compound, and diallyl phthalate (DAP).
[0074] The compound having an acenaphthylene structure in the molecule is an acenaphthylene compound. Examples of the acenaphthylene compound include acenaphthylene, alkylacenaphthylenes, halogenated acenaphthylenes, and phenylacenaphthylenes. Examples of the alkylacenaphthylenes include 1-methylacenaphthylene, 3-methylacenaphthylene, 4-methylacenaphthylene, 5-methylacenaphthylene, 1-ethylacenaphthylene, 3-ethylacenaphthylene, 4-ethylacenaphthylene, and 5-ethylacenaphthylene. Examples of the halogenated acenaphthylenes include 1-chloroacenaphthylene, 3-chloroacenaphthylene, 4-chloroacenaphthylene, 5-chloroacenaphthylene, 1-bromoacenaphthylene, 3-bromoacenaphthylene, 4-bromoacenaphthylene, and 5-bromoacenaphthylene. Examples of the phenylacenaphthylenes include 1-phenylacenaphthylene, 3-phenylacenaphthylene, 4-phenylacenaphthylene, and 5-phenylacenaphthylene. The acenaphthylene compound may be a monofunctional acenaphthylene compound having one acenaphthylene structure in the molecule as described above, or a polyfunctional acenaphthylene compound having two or more acenaphthylene structures in the molecule.
[0075] The compound having a maleimide group in the molecule is a maleimide compound. Examples of the maleimide compound include a monofunctional maleimide compound having one maleimide group in the molecule, a polyfunctional maleimide compound having two or more maleimide groups in the molecule, and a modified maleimide compound. Examples of the modified maleimide compound include a modified maleimide compound in which a part of the molecule is modified with an amine compound, a modified maleimide compound in which a part of the molecule is modified with a silicone compound, and a modified maleimide compound in which a part of the molecule is modified with an amine compound and a silicone compound.
[0076] The compound having an isocyanurate group in the molecule is an isocyanurate compound. Examples of the isocyanurate compound include compounds further having an alkenyl group in the molecule (alkenyl isocyanurate compounds), such as triallyl isocyanurate (TAIC) and other trialkenyl isocyanurate compounds.
[0077] The curing agent is not limited to the above-mentioned exemplary compounds, but among the above, for example, styrene, the styrene derivative, the acrylate compound, the methacrylate compound, the vinyl compound, the allyl compound, the maleimide compound, the acenaphthylene compound, and the isocyanurate compound are preferable, and the polyfunctional acrylate compound, the polyfunctional methacrylate compound, the polyfunctional vinyl compound, the acenaphthylene compound, and the allyl compound are more preferable. Moreover, the polyfunctional vinyl compound is preferably divinylbenzene. Moreover, the acenaphthylene compound is preferably acenaphthylene. Moreover, the allyl compound is preferably an allyl isocyanurate compound having two or more allyl groups in the molecule, and more preferably triallyl isocyanurate (TAIC). Moreover, the polyfunctional methacrylate compound is preferably a dimethacrylate compound, and more preferably tricyclodecane dimethanol dimethacrylate (DCP).
[0078] The curing agent may be used alone or in combination of two or more kinds.
[0079] The curing agent preferably has a weight average molecular weight of 100 to 5000, more preferably 100 to 4000, and even more preferably 100 to 3000. If the weight average molecular weight of the curing agent is too low, the curing agent may be easily volatilized from the compounding components of the resin composition. If the weight average molecular weight of the curing agent is too high, the viscosity of the varnish of the resin composition and the melt viscosity during heat molding may be too high. Therefore, if the weight average molecular weight of the curing agent is within such a range, a resin composition having excellent heat resistance of the cured product can be obtained. This is considered to be because the resin composition containing the polymer can be suitably cured by the reaction with the polymer. Here, the weight average molecular weight may be measured by a general molecular weight measurement method, and specifically, a value measured using gel permeation chromatography (GPC) may be mentioned.
[0080] The average number of functional groups per molecule of the curing agent that contribute to the reaction with the polymer (number of functional groups) varies depending on the weight average molecular weight of the curing agent, but is preferably 1 to 20, more preferably 2 to 18. If the number of functional groups is too small, it tends to be difficult to obtain a cured product with sufficient heat resistance. If the number of functional groups is too large, the reactivity becomes too high, and there is a risk of problems such as a decrease in the storage stability of the resin composition or a decrease in the flowability of the resin composition.
[0081] (Polyphenylene ether compound) The resin composition preferably further contains a polyphenylene ether compound. The polyphenylene ether compound is not particularly limited as long as it has a polyphenylene ether chain in the molecule. Examples of the polyphenylene ether compound include polyphenylene ether compounds having an unsaturated double bond in the molecule.
[0082] Examples of the polyphenylene ether compound having an unsaturated double bond in the molecule include polyphenylene ether compounds having a substituent having an unsaturated double bond in the molecule, such as polyphenylene ether compounds having a substituent having an unsaturated double bond at a molecular end, such as modified polyphenylene ether compounds whose terminals are modified with a substituent having an unsaturated double bond.
[0083] The substituent having an unsaturated double bond is not particularly limited. As the substituent, for example, a substituent represented by the following formula (8) and a substituent represented by the following formula (9) are preferably used. That is, the polyphenylene ether compound preferably contains a polyphenylene ether compound having at least one of a group represented by the following formula (8) and a group represented by the following formula (9) in the molecule.
[0084] [ka] In formula (8), p represents an integer of 0 to 10. A represents an arylene group. 12 ~R 14 are independent of each other. That is, R 12 ~R 14 may be the same or different groups. 12 ~R 14 represents a hydrogen atom or an alkyl group.
[0085] In addition, in formula (8), when p is 0, Z A is directly bonded to the end of the polyphenylene ether.
[0086] The arylene group is not particularly limited. Examples of the arylene group include monocyclic aromatic groups such as phenylene groups, and polycyclic aromatic groups in which the aromatic ring is not monocyclic but is polycyclic aromatic such as naphthalene ring. The arylene group also includes derivatives in which a hydrogen atom bonded to the aromatic ring is substituted with a functional group such as an alkenyl group, an alkynyl group, a formyl group, an alkylcarbonyl group, an alkenylcarbonyl group, or an alkynylcarbonyl group. The alkyl group is not particularly limited, and is preferably an alkyl group having 1 to 18 carbon atoms, more preferably an alkyl group having 1 to 10 carbon atoms. Specific examples include a methyl group, an ethyl group, a propyl group, a hexyl group, and a decyl group.
[0087] [ka] In formula (9), R 15 represents a hydrogen atom or an alkyl group. The alkyl group is not particularly limited, and is preferably, for example, an alkyl group having 1 to 18 carbon atoms, and more preferably an alkyl group having 1 to 10 carbon atoms. Specific examples include a methyl group, an ethyl group, a propyl group, a hexyl group, and a decyl group.
[0088] A preferred specific example of the substituent represented by the formula (8) is a substituent containing a vinylbenzyl group. An example of the substituent containing a vinylbenzyl group is a substituent represented by the following formula (10). An example of the substituent represented by the formula (9) is an acrylate group or a methacrylate group.
[0089] [ka]
[0090] More specifically, the substituent includes a vinylbenzyl group (ethenylbenzyl group), a vinylphenyl group, an acrylate group, a methacrylate group, etc. The vinylbenzyl group may be any one of an o-ethenylbenzyl group, an m-ethenylbenzyl group, and a p-ethenylbenzyl group, or may be two or more of them.
[0091] The polyphenylene ether compound has a polyphenylene ether chain in the molecule, and preferably has, for example, a repeating unit represented by the following formula (11) in the molecule.
[0092] [ka] In formula (11), t is an integer of 1 to 50. 16 ~R 19 are independent of each other. That is, R 16 ~R 19 may be the same or different groups. 16 ~R 19 represents a hydrogen atom, an alkyl group, an alkenyl group, an alkynyl group, a formyl group, an alkylcarbonyl group, an alkenylcarbonyl group, or an alkynylcarbonyl group, among which a hydrogen atom and an alkyl group are preferred.
[0093] R 16 ~R 19 Specific examples of the functional groups mentioned in the above include the following:
[0094] The alkyl group is not particularly limited, but is preferably, for example, an alkyl group having 1 to 18 carbon atoms, and more preferably an alkyl group having 1 to 10 carbon atoms. Specific examples include a methyl group, an ethyl group, a propyl group, a hexyl group, and a decyl group.
[0095] The alkenyl group is not particularly limited, but is preferably an alkenyl group having 2 to 18 carbon atoms, and more preferably an alkenyl group having 2 to 10 carbon atoms. Specific examples include a vinyl group, an allyl group, and a 3-butenyl group.
[0096] The alkynyl group is not particularly limited, but for example, an alkynyl group having 2 to 18 carbon atoms is preferable, and an alkynyl group having 2 to 10 carbon atoms is more preferable. Specific examples include an ethynyl group, a prop-2-yn-1-yl group (propargyl group), and the like.
[0097] The alkylcarbonyl group is not particularly limited as long as it is a carbonyl group substituted with an alkyl group, and is preferably, for example, an alkylcarbonyl group having 2 to 18 carbon atoms, and more preferably an alkylcarbonyl group having 2 to 10 carbon atoms. Specific examples include an acetyl group, a propionyl group, a butyryl group, an isobutyryl group, a pivaloyl group, a hexanoyl group, an octanoyl group, and a cyclohexylcarbonyl group.
[0098] The alkenylcarbonyl group is not particularly limited as long as it is a carbonyl group substituted with an alkenyl group, but for example, an alkenylcarbonyl group having 3 to 18 carbon atoms is preferable, and an alkenylcarbonyl group having 3 to 10 carbon atoms is more preferable. Specific examples include an acryloyl group, a methacryloyl group, and a crotonoyl group.
[0099] The alkynylcarbonyl group is not particularly limited as long as it is a carbonyl group substituted with an alkynyl group, but for example, an alkynylcarbonyl group having 3 to 18 carbon atoms is preferable, and an alkynylcarbonyl group having 3 to 10 carbon atoms is more preferable. Specific examples include a propioloyl group.
[0100] The weight average molecular weight (Mw) of the polyphenylene ether compound is not particularly limited. Specifically, it is preferably 500 to 5000, more preferably 800 to 4000, and further preferably 1000 to 3000. The weight average molecular weight may be measured by a general molecular weight measurement method, and specifically, it may be a value measured using gel permeation chromatography (GPC). In addition, when the polyphenylene ether compound has a repeating unit represented by the formula (11) in the molecule, t is preferably a numerical value that causes the weight average molecular weight of the polyphenylene ether compound to be within such a range. Specifically, t is preferably 1 to 50.
[0101] When the weight average molecular weight of the polyphenylene ether compound is within such a range, the compound has excellent low dielectric properties that polyphenylene ether has, and the cured product has excellent heat resistance and excellent moldability. This is believed to be due to the following. When the weight average molecular weight of a normal polyphenylene ether is within such a range, the cured product has a relatively low molecular weight, so the heat resistance tends to decrease. In this respect, since the polyphenylene ether compound according to the present embodiment has an unsaturated double bond at the end, it is believed that the cured product has sufficiently high heat resistance. In addition, when the weight average molecular weight of the polyphenylene ether compound is within such a range, the compound has a relatively low molecular weight, so it is believed that the compound has excellent moldability. Therefore, it is believed that such a polyphenylene ether compound not only has excellent heat resistance but also has excellent moldability.
[0102] The average number of the substituents (terminal functional group number) at the molecular end per molecule of the polyphenylene ether compound is not particularly limited. Specifically, it is preferably 1 to 5, more preferably 1 to 3, and even more preferably 1.5 to 3. If the number of terminal functional groups is too small, it is difficult to obtain a cured product with sufficient heat resistance. If the number of terminal functional groups is too large, the reactivity becomes too high, and there is a possibility that problems such as a decrease in the storage stability of the resin composition or a decrease in the fluidity of the resin composition may occur. That is, when such a polyphenylene ether is used, there is a possibility that a molding defect such as the generation of voids during multilayer molding may occur due to insufficient fluidity, and a highly reliable printed wiring board may be difficult to obtain.
[0103] The number of terminal functional groups of the polyphenylene ether compound may be a numerical value representing the average value of the above-mentioned substituents per molecule of all polyphenylene ether compounds present in 1 mole of the polyphenylene ether compound. The number of terminal functional groups can be measured, for example, by measuring the number of hydroxyl groups remaining in the obtained polyphenylene ether compound and calculating the reduction from the number of hydroxyl groups of the polyphenylene ether before modification. The reduction from the number of hydroxyl groups of the polyphenylene ether before modification is the number of terminal functional groups. The number of hydroxyl groups remaining in the polyphenylene ether compound can be measured by adding a quaternary ammonium salt (tetraethylammonium hydroxide) that associates with hydroxyl groups to a solution of the polyphenylene ether compound and measuring the UV absorbance of the mixed solution.
[0104] The intrinsic viscosity of the polyphenylene ether compound is not particularly limited. Specifically, it may be 0.03 to 0.12 dl / g, preferably 0.04 to 0.11 dl / g, and more preferably 0.06 to 0.095 dl / g. If the intrinsic viscosity is too low, the molecular weight tends to be low, and low dielectric properties such as low dielectric constant and low dielectric loss tangent tend to be difficult to obtain. If the intrinsic viscosity is too high, the viscosity is high, sufficient fluidity cannot be obtained, and the moldability of the cured product tends to decrease. Therefore, if the intrinsic viscosity of the polyphenylene ether compound is within the above range, excellent heat resistance and moldability of the cured product can be realized.
[0105] The intrinsic viscosity here is the intrinsic viscosity measured in methylene chloride at 25° C., and more specifically, for example, the value measured by a viscometer using a 0.18 g / 45 ml methylene chloride solution (liquid temperature 25° C.) As the viscometer, for example, the AVS500 Visco System manufactured by Schott Corporation can be mentioned.
[0106] Examples of the polyphenylene ether compound include a modified polyphenylene ether compound represented by the following formula (12) and a modified polyphenylene ether compound represented by the following formula (13). As the polyphenylene ether compound, these modified polyphenylene ether compounds may be used alone or in combination of these two modified polyphenylene ether compounds.
[0107] [ka]
[0108] [ka]
[0109] In formula (12) and formula (13), R 20 ~R 27 And R 28 ~R 35each independently represents a hydrogen atom, an alkyl group, an alkenyl group, an alkynyl group, a formyl group, an alkylcarbonyl group, an alkenylcarbonyl group, or an alkynylcarbonyl group. X1 and X2 each independently represent a substituent having a carbon-carbon unsaturated double bond. A and B represent repeating units represented by the following formula (14) and formula (15), respectively. In addition, in formula (13), Y represents a linear, branched, or cyclic hydrocarbon having 20 or less carbon atoms.
[0110] [ka]
[0111] [ka]
[0112] In the formulas (14) and (15), m and n each represent an integer of 0 to 20. 36 ~R 39 And R 40 ~R 43 each independently represents a hydrogen atom, an alkyl group, an alkenyl group, an alkynyl group, a formyl group, an alkylcarbonyl group, an alkenylcarbonyl group, or an alkynylcarbonyl group.
[0113] The modified polyphenylene ether compound represented by the formula (12) and the modified polyphenylene ether compound represented by the formula (13) are not particularly limited as long as they satisfy the above-mentioned constitution. 20 ~R 27 And R 28 ~R 35 are independent of each other as described above. That is, R 20 ~R 27 And R 28 ~R 35 may be the same or different groups. 20 ~R 27 And R 28 ~R 35represents a hydrogen atom, an alkyl group, an alkenyl group, an alkynyl group, a formyl group, an alkylcarbonyl group, an alkenylcarbonyl group, or an alkynylcarbonyl group, among which a hydrogen atom and an alkyl group are preferred.
[0114] In the formula (14) and the formula (15), m and n each preferably represent a value of 0 to 20 as described above. In addition, it is preferable that m and n represent a value such that the sum of m and n is 1 to 30. Therefore, it is more preferable that m represents a value of 0 to 20, n represents a value of 0 to 20, and the sum of m and n represents a value of 1 to 30. In addition, R 36 ~R 39 And R 40 ~R 43 are independent of each other. That is, R 36 ~R 39 And R 40 ~R 43 may be the same or different groups. 36 ~R 39 And R 40 ~R 43 represents a hydrogen atom, an alkyl group, an alkenyl group, an alkynyl group, a formyl group, an alkylcarbonyl group, an alkenylcarbonyl group, or an alkynylcarbonyl group, among which a hydrogen atom and an alkyl group are preferred.
[0115] R 20 ~R 43 is R in the above formula (11). 16 ~R 19 is the same as:
[0116] In the formula (13), as described above, Y is a linear, branched, or cyclic hydrocarbon having a carbon number of 20 or less. Examples of Y include a group represented by the following formula (16).
[0117] [ka] In the formula (16), R 44 and R 45are each independently a hydrogen atom or an alkyl group. Examples of the alkyl group include a methyl group. Examples of the group represented by formula (16) include a methylene group, a methylmethylene group, and a dimethylmethylene group, and among these, a dimethylmethylene group is preferred.
[0118] In the formula (12) and the formula (13), X1 and X2 are each independently a substituent having a carbon-carbon unsaturated double bond. The substituents X1 and X2 are not particularly limited as long as they are a substituent having a carbon-carbon unsaturated double bond. Examples of the substituents X1 and X2 include the substituents represented by the above formula (8). In the modified polyphenylene ether compound represented by the formula (12) and the modified polyphenylene ether compound represented by the formula (13), X1 and X2 may be the same or different substituents.
[0119] More specific examples of the modified polyphenylene ether compound represented by the formula (12) include modified polyphenylene ether compounds represented by the following formula (17).
[0120] [ka]
[0121] More specific examples of the modified polyphenylene ether compound represented by the formula (13) include a modified polyphenylene ether compound represented by the following formula (18) and a modified polyphenylene ether compound represented by the following formula (19).
[0122] [ka]
[0123] [ka]
[0124] In the above formulas (17) to (19), m and n are the same as m and n in the above formulas (14) and (15). 12 ~R 14 , p, and Z A is R in the above formula (8). 12 ~R 14 , p, and Z A In the above formula (18) and formula (19), Y is the same as Y in the above formula (13). In the above formula (19), R 15 is R in the above formula (9). 15 is the same as:
[0125] In the modified polyphenylene ether compound, the average number of the substituents (number of terminal functional groups) at the molecular terminals per molecule of the modified polyphenylene ether compound may be in the range described above. For example, in the case of the modified polyphenylene ether compounds represented by the above formulas (17) to (19), specifically, the average number is preferably 1 to 2, and more preferably 1.5 to 2.
[0126] The method for synthesizing the modified polyphenylene ether compound used in the present embodiment is not particularly limited as long as it is possible to synthesize a modified polyphenylene ether compound whose terminal is modified by a substituent having a carbon-carbon unsaturated double bond.Specific examples include a method of reacting a polyphenylene ether with a compound in which a substituent having a carbon-carbon unsaturated double bond and a halogen atom are bonded.
[0127] Examples of the compound in which a substituent having a carbon-carbon unsaturated double bond is bonded to a halogen atom include compounds in which a substituent represented by the formulas (8) to (10) is bonded to a halogen atom. Specific examples of the halogen atom include a chlorine atom, a bromine atom, an iodine atom, and a fluorine atom, and among these, a chlorine atom is preferred. More specific examples of the compound in which a substituent having a carbon-carbon unsaturated double bond is bonded to a halogen atom include p-chloromethylstyrene and m-chloromethylstyrene.
[0128] The raw material polyphenylene ether is not particularly limited as long as it can finally synthesize a predetermined modified polyphenylene ether compound. Specifically, polyphenylene ethers composed of 2,6-dimethylphenol and at least one of a bifunctional phenol and a trifunctional phenol, and poly(2,6-dimethyl-1,4-phenylene oxide) and the like, which are mainly composed of polyphenylene ether, can be mentioned. In addition, the bifunctional phenol is a phenolic compound having two phenolic hydroxyl groups in the molecule, for example, tetramethylbisphenol A, etc. In addition, the trifunctional phenol is a phenolic compound having three phenolic hydroxyl groups in the molecule.
[0129] The synthesis method of the modified polyphenylene ether compound includes the above-mentioned method. Specifically, the above-mentioned polyphenylene ether and a compound in which a substituent having a carbon-carbon unsaturated double bond and a halogen atom are bonded are dissolved in a solvent and stirred. By doing so, the polyphenylene ether reacts with the compound in which a substituent having a carbon-carbon unsaturated double bond and a halogen atom are bonded, and the modified polyphenylene ether compound used in the present embodiment is obtained.
[0130] The reaction is preferably carried out in the presence of an alkali metal hydroxide. By doing so, it is believed that the reaction proceeds favorably. This is believed to be because the alkali metal hydroxide functions as a dehydrohalogenation agent, specifically, a dehydrochlorination agent. That is, it is believed that the alkali metal hydroxide removes hydrogen halide from the phenol group of the polyphenylene ether and the compound in which a substituent having a carbon-carbon unsaturated double bond and a halogen atom are bonded, and thereby the substituent having a carbon-carbon unsaturated double bond is bonded to the oxygen atom of the phenol group instead of the hydrogen atom of the phenol group of the polyphenylene ether.
[0131] The alkali metal hydroxide is not particularly limited as long as it can act as a dehalogenating agent, and examples thereof include sodium hydroxide, etc. The alkali metal hydroxide is usually used in the form of an aqueous solution, specifically, an aqueous sodium hydroxide solution.
[0132] The reaction conditions such as reaction time and reaction temperature vary depending on the compound in which a substituent having a carbon-carbon unsaturated double bond is bonded to a halogen atom, and are not particularly limited as long as the reaction proceeds favorably under the conditions. Specifically, the reaction temperature is preferably room temperature to 100°C, more preferably 30 to 100°C. The reaction time is preferably 0.5 to 20 hours, more preferably 0.5 to 10 hours.
[0133] The solvent used in the reaction is not particularly limited as long as it can dissolve the polyphenylene ether and the compound in which a substituent having a carbon-carbon unsaturated double bond and a halogen atom are bonded, and does not inhibit the reaction between the polyphenylene ether and the compound in which a substituent having a carbon-carbon unsaturated double bond and a halogen atom are bonded.Specific examples include toluene and the like.
[0134] The above reaction is preferably carried out in the presence of not only an alkali metal hydroxide but also a phase transfer catalyst. That is, the above reaction is preferably carried out in the presence of an alkali metal hydroxide and a phase transfer catalyst. It is believed that the above reaction proceeds more favorably by doing so. This is believed to be due to the following. It is believed that the phase transfer catalyst is a catalyst that has the function of incorporating an alkali metal hydroxide, is soluble in both a polar solvent phase such as water and a non-polar solvent phase such as an organic solvent, and can move between these phases. Specifically, when an aqueous sodium hydroxide solution is used as the alkali metal hydroxide and an organic solvent such as toluene, which is not compatible with water, is used as the solvent, even if the aqueous sodium hydroxide solution is dropped into the solvent being used for the reaction, the solvent and the aqueous sodium hydroxide solution are separated, and it is believed that the sodium hydroxide is unlikely to move to the solvent. In that case, it is believed that the aqueous sodium hydroxide solution added as the alkali metal hydroxide is unlikely to contribute to promoting the reaction. On the other hand, when the reaction is carried out in the presence of an alkali metal hydroxide and a phase transfer catalyst, the alkali metal hydroxide is transferred to the solvent while being incorporated in the phase transfer catalyst, and the aqueous sodium hydroxide solution is likely to contribute to promoting the reaction. Therefore, when the reaction is carried out in the presence of an alkali metal hydroxide and a phase transfer catalyst, the reaction is believed to proceed more favorably.
[0135] The phase transfer catalyst is not particularly limited, but examples thereof include quaternary ammonium salts such as tetra-n-butylammonium bromide.
[0136] The resin composition used in the present embodiment preferably contains, as the polyphenylene ether compound, the modified polyphenylene ether compound obtained as described above.
[0137] (Content) The content of the polymer is preferably 40 to 90 parts by mass, more preferably 50 to 90 parts by mass, based on 100 parts by mass of the total of the polymer and the curing agent. That is, the content of the polymer is preferably 40 to 90% by mass, based on 100 parts by mass of the total of the polymer and the curing agent. In addition, when the polyphenylene ether compound is contained in the resin composition, the content of the polymer is preferably 40 to 90 parts by mass, based on 100 parts by mass of the total of the polymer, the curing agent, and the polyphenylene ether compound. That is, the content of the polymer is preferably 40 to 90% by mass, based on 100 parts by mass of the total of the polymer, the curing agent, and the polyphenylene ether compound. In addition, the content of the curing agent is preferably 10 to 60 parts by mass, more preferably 10 to 50 parts by mass, based on 100 parts by mass of the total of the polymer and the curing agent. That is, the content ratio of the polymer and the curing agent is preferably 90:10 to 40:60 by mass ratio, and more preferably 90:10 to 50:50. If the content of each of the polymer and the curing agent is such that the above ratio is satisfied, the resin composition will have better heat resistance of the cured product. This is considered to be because the curing reaction between the polymer and the curing agent proceeds favorably. In addition, the resin composition may contain the polyphenylene ether compound, and in this case, the content of the polyphenylene ether compound is preferably 1 to 30 parts by mass, and more preferably 5 to 10 parts by mass, relative to 100 parts by mass of the total of the polymer, the curing agent, and the polyphenylene ether compound.
[0138] (Other Ingredients) The resin composition according to the present embodiment may contain components (other components) other than the polymer, the curing agent, and the polyphenylene ether compound, as necessary, within a range that does not impair the effects of the present invention. The other components contained in the resin composition according to the present embodiment may further contain additives such as, for example, a silane coupling agent, a flame retardant, an initiator, an antifoaming agent, an antioxidant, a heat stabilizer, an antistatic agent, an ultraviolet absorber, a dye or pigment, a lubricant, and an inorganic filler. In addition to the polymer, the curing agent, and the polyphenylene ether compound, the resin composition may also contain a thermosetting resin such as an epoxy resin.
[0139] The resin composition according to the present embodiment may contain a silane coupling agent as described above. The silane coupling agent may not only be contained in the resin composition, but may also be contained in the inorganic filler contained in the resin composition as a silane coupling agent that has been surface-treated in advance, or may be contained in the fibrous substrate as a silane coupling agent that has been surface-treated in advance. The silane coupling agent will be described later.
[0140] The resin composition according to the present embodiment may contain a flame retardant as described above. By containing a flame retardant, the flame retardancy of the cured product of the resin composition can be improved. The flame retardant is not particularly limited. Specifically, in fields where halogen-based flame retardants such as bromine-based flame retardants are used, for example, ethylene dipentabromobenzene, ethylene bistetrabromoimide, decabromodiphenyl oxide, and tetradecabromodiphenoxybenzene having a melting point of 300° C. or more are preferred. It is considered that the use of a halogen-based flame retardant can suppress the elimination of halogen at high temperatures and suppress the decrease in heat resistance. In addition, in fields where halogen-free is required, phosphate-based flame retardants, phosphazene-based flame retardants, bisdiphenylphosphine oxide-based flame retardants, and phosphinate-based flame retardants can be mentioned. A specific example of a phosphate-based flame retardant is a condensed phosphate ester of dixylenyl phosphate. A specific example of a phosphazene-based flame retardant is phenoxyphosphazene. A specific example of the bisdiphenylphosphine oxide flame retardant is xylylenebisdiphenylphosphine oxide. A specific example of the phosphinate flame retardant is a metal phosphinate of an aluminum salt of dialkylphosphinic acid. As the flame retardant, each of the flame retardants exemplified above may be used alone or in combination of two or more.
[0141] The resin composition according to the present embodiment may contain an initiator (reaction initiator) as described above. The resin composition may proceed with the curing reaction even if it is composed of the polymer and the curing agent. The curing reaction may proceed even if it is composed of only the polymer. However, depending on the process conditions, it may be difficult to raise the temperature to a level where the curing proceeds, so a reaction initiator may be added. The reaction initiator is not particularly limited as long as it can promote the curing reaction between the polymer and the curing agent. Specifically, examples of the reaction initiator include oxidizing agents such as α,α'-bis(t-butylperoxy-m-isopropyl)benzene, 2,5-dimethyl-2,5-di(t-butylperoxy)-3-hexyne, benzoyl peroxide, 3,3',5,5'-tetramethyl-1,4-diphenoquinone, chloranil, 2,4,6-tri-t-butylphenoxyl, t-butylperoxyisopropyl monocarbonate, and azobisisobutyronitrile. In addition, a carboxylate metal salt or the like may be used in combination as necessary. By doing so, the curing reaction can be further promoted. Among these, α,α'-bis(t-butylperoxy-m-isopropyl)benzene is preferably used. Since α,α'-bis(t-butylperoxy-m-isopropyl)benzene has a relatively high reaction initiation temperature, it can suppress the promotion of the curing reaction at the time when curing is not required, such as when drying the prepreg, and can suppress the deterioration of the storage stability of the polyphenylene ether resin composition. Furthermore, since α,α'-bis(t-butylperoxy-m-isopropyl)benzene has low volatility, it does not volatilize during drying or storage of the prepreg, and has good stability. Moreover, the reaction initiator may be used alone or in combination of two or more kinds.
[0142] The content of the initiator is not particularly limited, but for example, it is preferably 0.1 to 1.8, more preferably 0.1 to 1.5 parts by mass, and even more preferably 0.3 to 1.5 parts by mass, relative to 100 parts by mass of the total mass of the polymer, the curing agent, and the polyphenylene ether compound. If the content of the initiator is too small, the curing reaction between the polymer and the curing agent tends not to start properly. If the content of the initiator is too large, the dielectric tangent of the cured product of the obtained prepreg tends to increase, making it difficult to exhibit excellent low dielectric properties. Therefore, if the content of the initiator is within the above range, a cured product of the prepreg having excellent low dielectric properties can be obtained.
[0143] As described above, the resin composition according to the present embodiment may contain a filler such as an inorganic filler. Examples of the filler include those added to enhance the heat resistance and flame retardancy of the cured product of the resin composition, and are not particularly limited. In addition, by including a filler, the heat resistance and flame retardancy can be further enhanced. Specific examples of the filler include silica such as spherical silica, metal oxides such as alumina, titanium oxide, and mica, metal hydroxides such as aluminum hydroxide and magnesium hydroxide, talc, aluminum borate, barium sulfate, and calcium carbonate. Among these, silica, mica, and talc are preferable as the filler, and spherical silica is more preferable. In addition, the filler may be used alone or in combination of two or more types. In addition, the filler may be used as it is, or may be surface-treated with a silane coupling agent. Examples of the silane coupling agent include silane coupling agents having functional groups such as amino groups, vinyl groups, styryl groups, methacryloxy groups, and acryloxy groups in the molecule. That is, the silane coupling agent has at least one of an amino group, a methacryloxy group, a styryl group, a vinyl group, and an acryloxy group as a reactive functional group, and further includes a compound having a hydrolyzable group such as a methoxy group or an ethoxy group. The silane coupling agent is not particularly limited, and examples thereof include the following silane coupling agents. Examples of silane coupling agents having an amino group in the molecule include N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane, 1-aminopropyltrimethoxysilane, 2-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 1,2-diaminopropyltrimethoxysilane, 3-amino-1-propenyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-Dimethyl-butylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, N-(vinylbenzyl)-2-aminoethyl-3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, 3-(N-phenyl)aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropylethyldiethoxysilane, N-(2-aminoethyl)-3-aminopropyltriethoxysilane, 3-(N-styrylmethyl-2-aminoethylamino)propyltrimethoxysilane, bis(2-hydroxyethyl)-3-aminopropyltriethoxysilane, N-methylaminopropyltrimethoxysilane, N-(3-acryloxy-2- hydroxypropyl)-3-aminopropyltriethoxysilane, 4-aminobutyltriethoxysilane, (aminoethylaminomethyl)phenethyltrimethoxysilane, N-(2-aminoethyl-3-aminopropyl)tris(2-ethylhexoxy)silane, 6-(aminohexylaminopropyl)trimethoxysilane, aminophenyltrimethoxysilane, 3-(1-aminopropoxy)-3,3-dimethyl-1-propenyltrimethoxysilane, 3-aminopropyltris(methoxyethoxyethoxy)silane, 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, ω-aminoundecyltrimethoxysilane, 3-(2-N-benzylaminoethylaminopropyl)trimethoxysilane, bis(2-hydroxyethyl)-3-aminopropyltrimethoxysilane, (N,N-diethyl-3-aminopropyl)trimethoxysilane, (N,Examples of the silane coupling agent having a methacryloxy group in the molecule include 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, and 3-methacryloxypropylethyldiethoxysilane. Examples of the silane coupling agent having a styryl group in the molecule include p-styryltrimethoxysilane and p-styryltriethoxysilane. Examples of the silane coupling agent having a vinyl group in the molecule include vinyltriethoxysilane and vinyltrimethoxysilane. Examples of silane coupling agents having an acryloxy group in the molecule include 3-acryloxypropyltrimethoxysilane and 3-acryloxypropyltriethoxysilane. The filler may be an inorganic filler having a molybdenum compound present on at least a part of its surface. "Present on the surface" refers to a state in which a molybdenum compound is supported on at least a part of the surface of an inorganic filler (inorganic substance) other than a molybdenum compound, and a state in which a molybdenum compound is coated on at least a part of the surface of an inorganic filler (inorganic substance) other than a molybdenum compound. Examples of the molybdenum compound include molybdenum compounds that can be used as inorganic fillers, and more specifically, zinc molybdate, calcium molybdate, magnesium molybdate, and the like. The molybdenum compounds may be used alone or in combination of two or more kinds.
[0144] The content of the inorganic filler is preferably 30 to 280 parts by mass, more preferably 50 to 280 parts by mass, and even more preferably 50 to 250 parts by mass, relative to 100 parts by mass of the total mass of the polymer, the curing agent, and the polyphenylene ether compound. If the content of the inorganic filler is too small, the effect of the inorganic filler becomes insufficient, and for example, there is a tendency that the heat resistance and flame retardancy are not sufficiently improved. If the content of the inorganic filler is too high, the dielectric constant of the cured product of the resin composition and the cured product of the prepreg increases, and it tends to be difficult to exhibit excellent low dielectric properties. Therefore, if the content of the inorganic filler is within the above range, a cured product of the prepreg having excellent low dielectric properties can be obtained.
[0145] (copper foil) The copper foil is not particularly limited as long as the exposed surface of the copper-clad laminate has the above-mentioned chromium element amount and surface roughness when the copper-clad laminate is etched with a copper chloride solution. Specifically, the copper foil is not particularly limited as long as the chromium element amount measured by XPS on the exposed surface is 7.5 atomic % or less relative to the total element amount measured by XPS, and the surface roughness of the exposed surface is 2.0 μm or less in ten-point average roughness. The etching treatment of the copper-clad laminate when forming the exposed surface is an etching treatment with a copper chloride solution, which is a treatment to remove the copper foil. Specifically, the copper foil is etched using a cupric chloride solution at a solution temperature of 45° C. for 90 seconds (for example, when the copper foil has a thickness of 18 μm), and then washed with city water or pure water at room temperature to remove the copper foil.
[0146] The amount of chromium element measured by XPS in the exposed surface is 7.5 atomic % or less, preferably 7.0 atomic % or less, and more preferably 6.5 atomic % or less, based on the total amount of elements measured by XPS, as described above. If the amount of chromium element is too large, the interlayer adhesion is reduced, and when the obtained copper-clad laminate is heated, delamination is likely to occur, and the heat resistance tends to be reduced. Therefore, the smaller the amount of chromium element, the better, but in reality, the limit is about 0.1 atomic %. For this reason, the amount of chromium element is preferably 0.1 to 7.5 atomic %.
[0147] In addition, XPS can be measured by using a general X-ray photoelectron spectroscopy. Specifically, a PHI 5000 Versaprobe manufactured by ULVAC-PHI, Inc. can be used to irradiate X-rays onto a sample under vacuum and perform measurement.
[0148] The exposed surface preferably contains nitrogen elements that can be confirmed by XPS. The nitrogen elements that can be confirmed by XPS are those whose nitrogen element amount is equal to or greater than the detection limit of XPS, specifically, equal to or greater than 0.1 atomic %. The exposed surface preferably contains nitrogen elements whose nitrogen element amount measured by XPS is equal to or greater than 1.0 atomic %, more preferably equal to or greater than 2.5 atomic %, and even more preferably equal to or greater than 3.5 atomic %, based on the total element amount measured by XPS.
[0149] The present inventors found that when nitrogen elements that can be confirmed by XPS are present on the exposed surface, delamination is unlikely to occur even when the obtained wiring board is heated. As described above, the present inventors inferred that when a compound containing a chromium element is present as an etching residue, delamination is likely to occur when heated. On the other hand, when a compound containing a nitrogen element is present as an etching residue in an amount that can be confirmed by X-ray photoelectron spectroscopy, a certain amount of a compound containing a nitrogen element is also present on the surface of the insulating layer present between the wiring in the wiring board manufactured from the copper-clad laminate. It is believed that the compound containing the nitrogen element increases the interlayer adhesion between the insulating layers, making it difficult for delamination to occur. It is believed that this provides a copper-clad laminate that can be used to suitably manufacture wiring boards with higher heat resistance. For this reason, if the amount of the nitrogen element is too small, there is a tendency that the effect of suppressing the occurrence of delamination due to the presence of the nitrogen element cannot be fully exerted. In addition, the amount of the nitrogen element is preferably as large as possible, but in reality, the limit is about 5.0 atomic %. For this reason, the nitrogen element content is preferably 1.0 to 5.0 atomic %.
[0150] The nitrogen element is preferably derived from a nitrogen atom contained in a compound having an amino group, and more preferably derived from a nitrogen atom contained in a silane coupling agent having an amino group. The nitrogen element is derived from a nitrogen atom contained in a compound having an amino group, which means that the compound containing a nitrogen element present as an etching residue is a compound having an amino group. Specifically, such a copper foil is considered to be a copper foil having a layer treated with a silane coupling agent having an amino group in the molecule as a silane coupling agent layer described later. And, it is considered that this compound having an amino group, that is, a silane coupling agent having an amino group in the molecule, enhances the interlayer adhesion between the insulating layer and the insulating layer, and more effectively exerts the effect of making it difficult for delamination to occur. From this, it is considered that a copper-clad laminate capable of suitably manufacturing a wiring board with higher heat resistance can be obtained.
[0151] In addition to chromium (Cr) and nitrogen (N), the exposed surface may contain one or more elements selected from copper (Cu), carbon (C), oxygen (O), silicon (Si), nickel (Ni), zinc (Zn), and cobalt (Co) as elements that can be confirmed by XPS. The amount of each of these elements is, for example, preferably 0 to 90 atomic %, more preferably 0 to 80 atomic %, and even more preferably 0 to 70 atomic %, relative to the total amount of elements measured by XPS.
[0152] Specific examples of the copper foil include copper foils that have been subjected to various treatments on a copper foil base material. The treatments are not particularly limited as long as they are treatments that are applied to copper foils used in copper-clad laminates. Examples of the treatments include roughening treatment, heat-resistant treatment, rust-proofing treatment, and silane coupling agent treatment. The copper foil may be subjected to any one of the treatments or may be subjected to a combination of two or more of the treatments. In addition, when two or more of the treatments are performed, it is preferable to perform the roughening treatment, the heat-resistant treatment, the rust-proofing treatment, and the silane coupling agent treatment in this order.
[0153] The copper foil substrate may contain copper, and may be, for example, a foil substrate made of copper or a copper alloy. Examples of the copper alloy include an alloy containing copper and at least one selected from the group consisting of nickel, phosphorus, tungsten, arsenic, molybdenum, chromium, cobalt, and zinc.
[0154] The roughening treatment may be a roughening treatment generally performed when manufacturing copper foil, and is not particularly limited, but may include a treatment for forming roughening particles on the surface of the copper foil base material, which is the object to be treated. By this roughening treatment, the copper foil surface is covered with roughening particles containing copper or a copper alloy. The region where the roughening particles exist is also called a roughening layer. The copper foil may have a layer (roughening layer) formed by the roughening treatment.
[0155] The heat-resistant treatment may be a heat-resistant treatment generally performed when manufacturing copper foil, and is not particularly limited, but may be, for example, a treatment to form a heat-resistant layer containing nickel, cobalt, copper, and zinc, either alone or as an alloy. Even if the region formed by this heat-resistant treatment is not completely layered, it is still called a heat-resistant layer. The copper foil may have a layer (heat-resistant layer) formed by the heat-resistant treatment.
[0156] The rust-proofing treatment may be a rust-proofing treatment generally performed when manufacturing copper foil, and is not particularly limited, but is preferably a treatment that forms a rust-proofing layer containing nickel. In addition, the rust-proofing treatment may be, for example, a chromate treatment. Even if the area formed by this rust-proofing treatment is not a complete layer, it is also called a rust-proofing layer. The copper foil may be one that has a layer (rust-proofing layer) formed by the rust-proofing treatment.
[0157] The silane coupling agent treatment may be a silane coupling agent treatment generally performed when manufacturing copper foil, and is not particularly limited, but may be, for example, a treatment in which a silane coupling agent is applied to the surface of the copper foil or the like that is the object to be treated. The silane coupling agent treatment may be drying or heating after applying a silane coupling agent. By treating with a silane coupling agent, an alkoxy group of the silane coupling agent reacts with copper or the like that constitutes the copper foil that is the object to be treated, and bonds. The region formed by this bonded silane coupling agent is a silane coupling agent layer. The copper foil may be one that has a layer (silane coupling agent layer) formed by the silane coupling agent treatment.
[0158] Specifically, the copper foil includes a copper foil having a copper foil base material and a coating layer disposed on the copper foil base material. The coating layer includes, for example, a roughened layer, a heat-resistant layer, an anti-rust layer, and a silane coupling agent layer. The copper foil may include these layers alone as the coating layer, or may include two or more layers laminated together. In addition, when the coating layer is made of a plurality of layers, it is preferable that the roughened layer, the heat-resistant layer, the anti-rust layer, and the silane coupling agent layer are provided in this order from the copper foil base material.
[0159] The roughened layer may be, for example, a layer containing roughened particles containing copper or a copper alloy. The copper alloy is the same as the copper alloy in the copper foil base material. The roughened layer may be obtained by roughening the copper foil base material. The roughened layer may be, for example, a layer in which particles containing a simple substance or an alloy such as nickel, cobalt, copper, and zinc are formed as secondary particles and tertiary particles after roughening particles obtained by roughening the copper foil base material are formed. That is, the roughened layer may be, for example, a layer containing not only the roughened particles but also particles containing a simple substance or an alloy such as nickel, cobalt, copper, and zinc.
[0160] The heat-resistant layer may be a layer containing nickel, cobalt, copper, or zinc as a single element or an alloy thereof. The heat-resistant layer may be a single layer or a layer having two or more layers. For example, the heat-resistant layer may be a layer in which a nickel layer and a zinc layer are laminated.
[0161] The anticorrosive layer may be, for example, a layer containing chromium, such as a chromate-treated layer, etc. The anticorrosive layer may be obtained, for example, by subjecting a copper foil base material provided with the heat-resistant layer, etc., to a chromate treatment.
[0162] The silane coupling agent layer is a layer obtained by treating a copper foil base material provided with the rust-preventive layer or the like with a silane coupling agent. For example, a layer obtained by treating a copper foil base material provided with the rust-preventive layer or the like with a silane coupling agent can be mentioned.
[0163] Examples of the silane coupling agent include a silane coupling agent having an amino group in the molecule, and a silane coupling agent having a carbon-carbon unsaturated double bond in the molecule.
[0164] The silane coupling agent having an amino group in the molecule includes compounds having an amino group as a reactive functional group and further having a hydrolyzable group such as a methoxy group or an ethoxy group. Specific examples of the silane coupling agent having an amino group in the molecule include N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane, 1-aminopropyltrimethoxysilane, 2-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 1,2-diaminopropyltrimethoxysilane, 3-amino-1-propenyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, N-(vinylbenzyl)-2-aminoethyl-3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyl)-3-aminopropylmethyldimethoxysilane, 3-(N-phenyl)aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropylethyldiethoxysilane, N-(2-aminoethyl)-3-aminopropyltriethoxysilane, 3-(N-styrylmethyl-2-aminoethylamino)propyltrimethoxysilane, bis(2-hydroxyethyl)-3-aminopropyltriethoxysilane, N-methylaminopropyltrimethoxysilane, N-(3-acryloxy-2-hydroxypropyl)-3-aminopropyltriethoxysilane, 4-aminobutyltriethoxysilane, (aminoethylaminomethyl)phenethyltrimethoxysilane, N-(2-aminoethyl-3-aminopropyl)tris(2-ethylhexoxy)silane, 6-(aminohexylaminopropyl)trimethoxysilane, aminophenyltrimethoxysilane, 3-(1-aminopropoxy)-3,Examples of the silane include 3-dimethyl-1-propenyltrimethoxysilane, 3-aminopropyltris(methoxyethoxyethoxy)silane, 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, ω-aminoundecyltrimethoxysilane, 3-(2-N-benzylaminoethylaminopropyl)trimethoxysilane, bis(2-hydroxyethyl)-3-aminopropyltrimethoxysilane, (N,N-diethyl-3-aminopropyl)trimethoxysilane, (N,N-dimethyl-3-aminopropyl)trimethoxysilane, N-methylaminopropyltrimethoxysilane, N-phenylaminopropyltriethoxysilane, and 3-(N-styrylmethyl-2-aminoethylamino)propyltriethoxysilane.
[0165] Specific examples of the silane coupling agent having a carbon-carbon unsaturated double bond in the molecule include silane coupling agents having at least one functional group selected from the group consisting of methacryloxy, styryl, vinyl, and acryloxy groups. That is, the silane coupling agent has at least one of methacryloxy, styryl, vinyl, and acryloxy groups as a reactive functional group, and further includes compounds having hydrolyzable groups such as methoxy and ethoxy groups. Examples of the silane coupling agent having a carbon-carbon unsaturated double bond in the molecule include the following silane coupling agents. Examples of the silane coupling agent having a methacryloxy group in the molecule include 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, and 3-methacryloxypropylethyldiethoxysilane. Examples of silane coupling agents having a styryl group in the molecule include p-styryltrimethoxysilane and p-styryltriethoxysilane. Examples of silane coupling agents having a vinyl group in the molecule include vinyltriethoxysilane and vinyltrimethoxysilane. Examples of silane coupling agents having an acryloxy group in the molecule include 3-acryloxypropyltrimethoxysilane and 3-acryloxypropyltriethoxysilane.
[0166] The amount of the chromium element can be adjusted, for example, by adjusting the thickness of a layer containing chromium, such as a chromate layer, in the coating layer.
[0167] The nitrogen element can be present by forming a layer using a silane coupling agent having an amino group in the molecule as the silane coupling agent layer.Furthermore, the amount (amount of nitrogen element) can be adjusted by adjusting the thickness of the layer obtained by using a silane coupling agent having an amino group in the molecule as the silane coupling agent layer.
[0168] The average roughness of the exposed surface is 2.0 μm or less, preferably 1.8 μm or less, and more preferably 1.5 μm or less, in ten-point mean roughness. The lower the surface roughness of the exposed surface, that is, the higher the smoothness of the exposed surface, the higher the smoothness of the contact surface between the copper foil and the insulating layer, which is preferable in terms of reducing loss during signal transmission. On the other hand, even if the surface roughness of the exposed surface is reduced, the limit is about 0.2 μm in ten-point mean roughness Rz. In addition, if the surface roughness of the exposed surface is too low, the smoothness of the contact surface between the copper foil and the insulating layer is also considered to be too high, and the adhesion between the copper foil and the insulating layer tends to decrease. From this point of view, the surface roughness of the exposed surface is preferably 0.2 μm or more in ten-point mean roughness Rz. Therefore, the surface roughness of the exposed surface is preferably 0.2 to 2.0 μm, more preferably 0.5 to 2.0 μm, further preferably 0.6 to 1.8 μm, and most preferably 0.6 to 1.5 μm, in terms of ten-point average roughness Rz.
[0169] The ten-point average roughness Rz, which is the surface roughness here, conforms to JIS B 0601:1994 and can be measured with a general surface roughness measuring instrument, etc. Specifically, for example, it can be measured using a surface roughness and shape measuring instrument (SURFCOM500DX) manufactured by Tokyo Seimitsu Co., Ltd.
[0170] The average roughness of the exposed surface can be adjusted by adjusting the average roughness of the surface of the copper foil that contacts the insulating layer. Specifically, the average roughness of the surface of the copper foil that contacts the insulating layer is preferably 0.5 to 2.0 μm in ten-point average roughness Rz. The copper foil has a surface with a large average roughness, that is, the so-called M surface, as the surface that contacts the insulating layer. The above-mentioned coating layer may be formed on this M surface. The surface of the copper foil with a small average roughness, that is, the so-called S surface, may have the above-mentioned coating layer formed thereon, as with the M surface, but may have only the anticorrosive layer formed thereon, or may not have the coating layer formed thereon.
[0171] (Manufacturing method) The resin composition used in this embodiment may be prepared in a varnish form and used. For example, when producing a prepreg, the resin composition may be prepared in a varnish form and used for the purpose of impregnating a substrate (fibrous substrate) for forming the prepreg. That is, the resin composition may be used as a varnish (resin varnish). In addition, in the resin composition used in this embodiment, the polymer, the curing agent, the polyphenylene ether compound, and the like are dissolved in the resin varnish. Such a varnish-like composition (resin varnish) is prepared, for example, as follows.
[0172] First, each component that can be dissolved in an organic solvent is put into the organic solvent and dissolved. At this time, heating may be performed as necessary. Then, a component that is not dissolved in the organic solvent, which is used as necessary, is added, and dispersed until a predetermined dispersion state is reached using a ball mill, a bead mill, a planetary mixer, a roll mill, or the like, to prepare a varnish-like composition. The organic solvent used here is not particularly limited as long as it dissolves the polymer and does not inhibit the curing reaction. Specific examples include toluene and methyl ethyl ketone (MEK), etc.
[0173] As described above, the insulating layer may contain not only the cured product of the resin composition but also a fibrous base material. Examples of the fibrous base material include the same fibrous base material as that contained in the prepreg described below.
[0174] Furthermore, by using the resin composition, not only the copper-clad laminate but also a prepreg, a resin-coated copper foil, and a wiring board can be obtained as described below. In this case, the varnish-like composition as described above may be used as the resin composition.
[0175] As shown in Fig. 2, the prepreg 1 includes the resin composition or a semi-cured product of the resin composition 2, and a fibrous base material 3. Examples of the prepreg 1 include those in which the fibrous base material 3 is present in the resin composition or the semi-cured product of the resin composition 2. That is, the prepreg 1 includes the resin composition or the semi-cured product of the resin composition 2, and the fibrous base material 3 present in the resin composition or the semi-cured product of the resin composition 2. Fig. 2 is a schematic cross-sectional view showing an example of the prepreg 1 according to this embodiment.
[0176] In this embodiment, the semi-cured product refers to a resin composition that has been partially cured to the extent that it can be further cured. That is, the semi-cured product refers to a resin composition that has been semi-cured (B-staged). For example, when the resin composition is heated, the viscosity of the resin composition first gradually decreases, and then the resin composition starts to cure, and the viscosity gradually increases. In this case, the semi-cured state may be a state between when the viscosity starts to increase and when the resin composition is completely cured.
[0177] The prepreg may be a prepreg having a semi-cured product of the resin composition as described above, or may be a prepreg having the uncured resin composition itself. That is, the prepreg may be a prepreg having a semi-cured product of the resin composition (the resin composition in the B stage) and a fibrous base material, or a prepreg having the resin composition before curing (the resin composition in the A stage) and a fibrous base material. Specifically, the prepreg may be a prepreg having a fibrous base material in the resin composition. The resin composition or the semi-cured product of the resin composition may be a prepreg obtained by drying and / or heating the resin composition.
[0178] The method for producing the prepreg is not particularly limited as long as it can produce the prepreg. For example, a method of impregnating a fibrous substrate with a resin composition, for example, a resin composition prepared in a varnish form. That is, the prepreg can be obtained by impregnating a fibrous substrate with the resin composition. The method of impregnation is not particularly limited as long as it can impregnate a fibrous substrate with the resin composition. For example, it is not limited to dipping, but includes a method using a roll, a die coat, and a bar coat, and spraying. In addition, as a method for producing a prepreg, after the impregnation, at least one of drying and heating may be performed on the fibrous substrate impregnated with the resin composition. That is, as a method for producing a prepreg, for example, a method of impregnating a fibrous substrate with a resin composition prepared in a varnish form and then drying it, a method of impregnating a fibrous substrate with a resin composition prepared in a varnish form and then heating it, and a method of impregnating a fibrous substrate with a resin composition prepared in a varnish form, drying it, and then heating it, etc. can be mentioned.
[0179] Specific examples of fibrous substrates used in producing prepregs include glass cloth, aramid cloth, polyester cloth, liquid crystal plastic (LCP) nonwoven fabric, glass nonwoven fabric, aramid nonwoven fabric, polyester nonwoven fabric, pulp paper, and linter paper. When glass cloth is used, a laminated board with excellent mechanical strength is obtained, and flattened glass cloth is particularly preferable. The glass cloth is not particularly limited, and is preferably, for example, glass cloth or glass yarn constituting the glass cloth, etc., having a relative dielectric constant of 5.0 or less and a dielectric loss tangent of 0.0033 or less. The relative dielectric constant is preferably 5.0 or less, more preferably 4.7 or less. The dielectric loss tangent is preferably 0.0033 or less, more preferably 0.0030 or less. The relative dielectric constant and dielectric loss tangent here are, for example, the relative dielectric constant and dielectric loss tangent at a frequency of 10 GHz. Specific examples of the glass cloth include E glass cloth, S glass cloth, NE glass cloth, L glass cloth, quartz glass (Q glass) cloth, QL glass cloth, and L2 glass cloth. The glass cloth may be used as it is, or may be surface-treated with a silane coupling agent. Examples of the silane coupling agent include silane coupling agents having at least one functional group in the molecule, such as an amino group, a methacryloxy group, a styryl group, a vinyl group, and an acryloxy group. That is, the silane coupling agent has at least one of an amino group, a methacryloxy group, a styryl group, a vinyl group, and an acryloxy group as a reactive functional group, and further includes a compound having a hydrolyzable group such as a methoxy group or an ethoxy group. The silane coupling agent is not particularly limited, but examples thereof include the following silane coupling agents. Examples of silane coupling agents having an amino group in the molecule include N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane, 1-aminopropyltrimethoxysilane, 2-aminopropyltrimethoxysilane,3-Aminopropyltrimethoxysilane, 1,2-diaminopropyltrimethoxysilane, 3-amino-1-propenyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, N-(vinylbenzyl)-2-aminoethyl-3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3- Aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, 3-(N-phenyl)aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropylethyldiethoxysilane, N-(2-aminoethyl)-3-aminopropyltriethoxysilane, 3-(N-styrylmethyl-2-aminoethylamino)propyltrimethoxysilane, bis(2-hydroxyethyl)-3-aminopropyltriethoxysilane, N-methylaminopropyltrimethoxysilane, N -(3-acryloxy-2-hydroxypropyl)-3-aminopropyltriethoxysilane, 4-aminobutyltriethoxysilane, (aminoethylaminomethyl)phenethyltrimethoxysilane, N-(2-aminoethyl-3-aminopropyl)tris(2-ethylhexoxy)silane, 6-(aminohexylaminopropyl)trimethoxysilane, aminophenyltrimethoxysilane, 3-(1-aminopropoxy)-3,3-dimethyl-1-propenyltrimethoxysilane, 3-aminopropyltris(methoxyethoxyethyl)silane, (N,N-diethyl-3-aminopropyl)trimethoxysilane, (N,N-dimethyl-3-aminopropyl)trimethoxysilane, N-methylaminopropyltrimethoxysilane, N-phenylaminopropyltriethoxysilane,and 3-(N-styrylmethyl-2-aminoethylamino)propyltriethoxysilane. Examples of silane coupling agents having a methacryloxy group in the molecule include 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, and 3-methacryloxypropylethyldiethoxysilane. Examples of silane coupling agents having a styryl group in the molecule include p-styryltrimethoxysilane and p-styryltriethoxysilane. Examples of silane coupling agents having a vinyl group in the molecule include vinyltriethoxysilane and vinyltrimethoxysilane. Examples of silane coupling agents having an acryloxy group in the molecule include 3-acryloxypropyltrimethoxysilane and 3-acryloxypropyltriethoxysilane. Specifically, the flattening process can be carried out, for example, by continuously pressing the glass cloth with a press roll at an appropriate pressure to compress the yarn into a flat shape. The thickness of the fibrous base material is generally, for example, 0.01 to 0.3 mm.
[0180] The resin composition (resin varnish) is impregnated into the fibrous substrate by immersion, coating, etc. This impregnation can be repeated multiple times as necessary. In addition, it is also possible to repeat the impregnation using multiple resin compositions with different compositions and concentrations, and to adjust the composition and impregnation amount to the final desired one.
[0181] The fibrous substrate impregnated with the resin composition (resin varnish) is heated under desired heating conditions, for example, for 1 to 10 minutes at 80 to 180° C. By heating, the solvent is volatilized from the resin varnish, and the solvent is reduced or removed to obtain a prepreg in an uncured (A stage) or semi-cured (B stage) state.
[0182] The method for producing the copper-clad laminate according to the present embodiment is not particularly limited as long as the copper-clad laminate can be produced. The method for producing the copper-clad laminate can be, for example, similar to the method for producing a general copper-clad laminate, except that the resin composition and the copper foil are used. For example, a method using the prepreg can be mentioned. A method for producing a copper-clad laminate using a prepreg can be mentioned, for example, a method in which one or more prepregs are stacked, and the copper foil is stacked on both sides or one side of the prepreg so that the copper foil and the prepreg are in contact with each other, and the stack is heated and pressurized to form an integrated laminate. That is, the method for producing the copper-clad laminate includes a step of obtaining the resin composition, a step of impregnating a fibrous base material with the resin composition to obtain a prepreg, and a step of laminating the copper foil on the prepreg and heating and pressurizing to obtain a copper-clad laminate comprising an insulating layer containing a cured product of the resin composition and a copper foil present in contact with at least one surface of the insulating layer. By this method, a copper-clad laminate having copper foil on both sides or a copper-clad laminate having copper foil on one side can be produced. The heating and pressing conditions can be appropriately set depending on the thickness of the laminate to be produced and the type of resin composition contained in the prepreg. For example, the temperature can be 170 to 210°C, the pressure can be 3.5 to 4 MPa, and the time can be 60 to 150 minutes. The copper-clad laminate can also be produced without using a prepreg. For example, a method can be used in which a varnish-like resin composition or the like is applied onto the copper foil, a layer containing a curable composition is formed on the copper foil, and then heating and pressing are performed.
[0183] [Wiring board] A wiring board according to another embodiment of the present invention includes wiring formed by partially removing the copper foil provided on the copper-clad laminate, and the insulating layer. That is, as shown in FIG. 3, this wiring board 21 includes the insulating layer 12 and wiring 14 formed by partially removing the copper foil provided on the copper-clad laminate on both sides of the insulating layer. The wiring board may also be provided in contact with only one side of the insulating layer. FIG. 3 is a cross-sectional view showing the configuration of the wiring board 21 according to this embodiment.
[0184] The wiring board 21 includes an insulating layer 12 and wiring 14 that is in contact with at least one surface of the insulating layer 12. Examples of the wiring board 21 include a wiring board in which a surface 15 of the insulating layer 12 that is between the wirings 14 has the following surface, similar to the exposed surface. The amount of chromium element measured by XPS on the surface 15 is 7.5 atomic % or less with respect to the total amount of elements measured by XPS. The surface roughness of the surface 15 is 2.0 μm or less in ten-point average roughness. Note that etching residue is thought to remain on the surface 15 that corresponds to the exposed surface, but the insulating layer 12 includes the surface 15 that corresponds to the exposed surface.
[0185] The insulating layer 12 may be a layer similar to the insulating layer of the copper-clad laminate. The wiring 17 may be, for example, a wiring formed by partially removing the copper foil of the copper-clad laminate. Examples of such wiring include wiring formed by subtractive, additive, semi-additive (Semi Additive Process: SAP), modified semi-additive (Modified Semi Additive Process: MSAP), chemical mechanical polishing (CMP), trench, inkjet, squeegee, transfer, and the like.
[0186] This copper-clad laminate has a high signal transmission speed and high heat resistance. This is believed to be due to the fact that the wiring board is obtained using the copper-clad laminate. Specifically, as described above, the amount of compounds containing chromium present between the wiring is small, and therefore the occurrence of delamination can be sufficiently suppressed. In addition, the high signal transmission speed is believed to be due to the fact that the insulating layer has a low dielectric constant and dielectric loss tangent, and further, the contact surface between the wiring and the insulating layer has a high smoothness, as described above.
[0187] The wiring board according to the present embodiment may have one insulating layer as shown in FIG. 3, or may have a plurality of insulating layers as shown in FIG. 4. When the wiring board has a plurality of insulating layers, the wiring may be disposed on the surfaces of the insulating layers as shown in FIG. 4, or may be disposed between the insulating layers. The wiring board 31 according to the present embodiment has a plurality of insulating layers 12 as shown in FIG. 4. In addition, in the wiring board 31, the wiring 14 is disposed between the insulating layers 12. FIG. 4 is a schematic cross-sectional view showing another example of the wiring board 31 according to the present embodiment.
[0188] The wiring board as shown in Fig. 4 is manufactured, for example, as follows. The prepreg is laminated on at least one side of the wiring board as shown in Fig. 3, and copper foil is laminated thereon as necessary, followed by hot-press molding. The copper foil on the surface of the laminate thus obtained is etched or otherwise processed to form wiring. In this manner, a multi-layer wiring board as shown in Fig. 4 can be manufactured.
[0189] Such a wiring board is a multi-layer wiring board having a high signal transmission speed and high heat resistance. Specifically, since the multi-layer wiring board has high heat resistance and is unlikely to cause delamination even when heated, even if the wiring is disposed between the insulating layers, it is possible to suppress delamination between the insulating layers.
[0190] [Copper foil with resin] A resin-coated copper foil according to another embodiment of the present invention comprises a resin layer and a copper foil present in contact with one surface of the resin layer. As shown in Fig. 5, this resin-coated copper foil 41 may comprise a resin layer 42 and a copper foil 43 arranged in contact with one surface of the resin layer. Fig. 5 is a cross-sectional view showing the configuration of the resin-coated copper foil 41 according to this embodiment.
[0191] The resin layer 42 contains the resin composition (the resin composition in the A stage) or the semi-cured product of the resin composition (the resin composition in the B stage) as described above. The resin layer may contain the resin composition or the semi-cured product of the resin composition, and may or may not contain a fibrous base material. The fibrous base material may be the same as the fibrous base material of the prepreg. The copper foil 43 is the same as the copper foil provided in the copper-clad laminate. When the resin layer provided in the resin-coated copper foil is cured, the amount of chromium element measured by X-ray photoelectron spectroscopy on the exposed surface where the copper foil in contact with the surface of the cured resin layer is etched with a copper chloride solution to expose the cured resin layer is 7.5 atomic % or less with respect to the total amount of elements measured by X-ray photoelectron spectroscopy, and the surface roughness of the exposed surface is 2.0 μm or less in ten-point average roughness.
[0192] Such a resin-coated copper foil can be suitably used to manufacture wiring boards having a higher signal transmission speed and higher heat resistance.
[0193] In such a resin-coated copper foil, the resin layer contains a resin composition containing the polymer or a semi-cured product of the resin composition. Therefore, when the resin-coated copper foil is used to manufacture a wiring board, the insulating layer obtained by curing the resin layer contains a cured product of the resin composition or the semi-cured product of the resin composition, which is considered to improve the heat resistance of the insulating layer.
[0194] When the resin layer provided on the resin-coated copper foil is cured, the copper foil in contact with the surface of the cured resin layer is etched with a copper chloride solution, and the resin layer is exposed on the exposed surface. If the amount of chromium present on the exposed surface as the etching residue is small as described above, when the resin-coated copper foil is used to manufacture a wiring board, the amount of chromium present on the surface of the insulating layer present between the wirings in the wiring board, i.e., the amount of compounds containing chromium, is small. From this, it is considered that the resin-coated copper foil has high heat resistance that can sufficiently suppress delamination even when heated.
[0195] From the above, it is considered that the resin-coated metal foil has high heat resistance.
[0196] The insulating layer obtained by curing the resin layer includes a cured product obtained by curing the resin composition or a semi-cured product of the resin composition. The cured product includes a cured product obtained by curing a resin composition containing the modified polyphenylene ether compound. Therefore, the insulating layer obtained by curing the resin layer has a low dielectric constant and dielectric loss tangent. For this reason, it is considered that this wiring board can reduce the transmission loss caused by the inductor around the wiring and can increase the transmission speed of signals.
[0197] In addition, since the surface roughness of the exposed surface is low, the smoothness of the contact surface between the copper foil and the resin layer is also considered to be high. Therefore, when the resin-coated copper foil is used in manufacturing a wiring board, the smoothness of the contact surface between the wiring and the insulating layer obtained by hardening the resin layer is also considered to be high. It is considered that the signal transmitted through the wiring is concentrated near the surface of the conductor constituting the wiring due to the skin effect. It is considered that this effect becomes more prominent as the signal transmitted through the wiring becomes higher in frequency. And, when the contact surface between the wiring and the insulating layer becomes smooth, the signal flowing through the wiring flows near the surface with high smoothness, so the transmission distance is shortened. Therefore, it is considered that this wiring board can reduce the transmission loss caused by the conductor forming the wiring and increase the transmission speed of the signal.
[0198] For these reasons, it is believed that this wiring board can reduce transmission loss caused by the conductors that form the wiring, as well as transmission loss caused by the dielectric materials around the wiring, and can increase the signal transmission speed.
[0199] From the above, it is considered that the resin-coated copper foil is a resin-coated copper foil that can be suitably used to manufacture wiring boards having high signal transmission speed and high heat resistance.
[0200] The method for producing the resin-coated copper foil according to the present embodiment is not particularly limited as long as it can produce the resin-coated copper foil. The method for producing the resin-coated copper foil can be the same as the general method for producing a resin-coated copper foil, except that the resin composition and the copper foil are used. For example, the resin composition, for example, a resin composition prepared in a varnish form, can be applied to the copper foil. That is, the resin-coated copper foil according to the embodiment of the present invention can be obtained by applying the resin composition to the copper foil. The method for applying the resin composition is not particularly limited as long as it can apply the resin composition to the copper foil. For example, a method using a roll, a die coat, and a bar coat, spraying, etc. can be used. In addition, the method for producing the resin-coated copper foil can include at least one of drying and heating the copper foil to which the resin composition has been applied after the application. That is, examples of the method for producing a resin-coated copper foil include a method of applying a resin composition prepared in a varnish state onto a copper foil and then drying it, a method of applying a resin composition prepared in a varnish state onto a copper foil and then heating it, and a method of applying a resin composition prepared in a varnish state onto a copper foil, drying it, and then heating it. The copper foil coated with the resin composition is heated under desired heating conditions, for example, at 80 to 180°C for 1 to 10 minutes, to obtain a resin-coated copper foil in an uncured (A stage) or semi-cured (B stage) state.
[0201] According to the present invention, it is possible to provide a copper-clad laminate and a resin-coated copper foil that can be used to suitably manufacture a wiring board having a high signal transmission speed and high heat resistance. Also, according to the present invention, it is possible to provide a wiring board having a high signal transmission speed and high heat resistance.
[0202] The present invention will be described in more detail below with reference to examples, but the scope of the present invention is not limited thereto. EXAMPLES
[0203] [Examples 1 to 7 and Comparative Examples 1 to 4] In the present examples, each component used in preparing the resin composition will be described.
[0204] (Polymer) Polymer: A polymer obtained by the following method.
[0205] 3.6 mol (468 g) of divinylbenzene, 2.2 mol (290.4 g) of ethylvinylbenzene, 9.2 mol (956.8 g) of styrene, and 15 mol (1532 g) of n-propyl acetate were charged into a 5.0 L reactor and stirred. The mixture obtained by this stirring was heated to 70° C., and then 600 mmol of boron trifluoride diethyl ether complex was added. The mixture was further stirred at 70° C. for 4 hours to react divinylbenzene, ethylvinylbenzene, and styrene. Then, a saturated aqueous sodium bicarbonate solution was added to the reaction solution in the reactor to stop the reaction. The organic layer separated by the addition was washed three times with pure water. The washed organic layer was subjected to reduced pressure devolatilization at 60° C. to obtain a polymer.
[0206] The obtained polymer was a polymer having a structural unit represented by the above formula (1) in the molecule [an aromatic polymer having a structural unit derived from a bifunctional aromatic compound in which two carbon-carbon unsaturated double bonds are bonded to an aromatic ring, a compound having structural units represented by the above formulas (5) to (7), weight average molecular weight Mw: 31,100, vinyl equivalent (equivalent of vinyl group contained in the structural unit represented by the above formula (1) in which R1 to R3 are hydrogen atoms): 380].
[0207] The vinyl equivalent of the vinyl group contained in the structural unit of the polymer represented by the formula (1) where R1 to R3 are hydrogen atoms (vinyl equivalent) was calculated by iodine value measurement by the Wiess method. Specifically, the compound to be measured was first dissolved in chloroform to a concentration of 0.3 g / 35 mL to 0.3 g / 25 mL. An excess amount of iodine chloride was added to the double bonds present in the solution. By doing so, the double bonds react with iodine chloride, and after the reaction has sufficiently progressed, the iodine remaining in the solution after the reaction is reduced to I3 by adding a 20% by mass aqueous potassium iodide solution to the solution after the reaction. - This I3 was extracted into the aqueous phase. - The aqueous phase into which was extracted was titrated with an aqueous sodium thiosulfate solution (0.1 mol / L sodium thiosulfate standard solution) to calculate the iodine value. The following formula was used to calculate the iodine value.
[0208] Iodine value = [(BA) x F x 1.269] / mass of compound (g) In the above formula, B represents the titer (cc) of 0.1 mol / L sodium thiosulfate standard solution required for the blank test, A represents the titer (cc) of 0.1 mol / L sodium thiosulfate standard solution required for neutralization, and F represents the titer of sodium thiosulfate.
[0209] (hardening agent) DVB: Divinylbenzene (a thermosetting curing agent with two carbon-carbon unsaturated double bonds at the molecular end, Nippon Steel & Sumitomo Metal Corporation's DVB810, molecular weight 130) TAIC: Triallyl isocyanurate (a thermosetting curing agent with three carbon-carbon unsaturated double bonds at the molecular end, TAIC manufactured by Nippon Kasei Co., Ltd., weight average molecular weight Mw249) Acenaphthylene: Acenaphthylene manufactured by JFE Chemical Corporation DCP: Tricyclodecane dimethanol dimethacrylate (NK Ester DCP manufactured by Shin-Nakamura Chemical Co., Ltd.) (Polyphenylene ether compounds: PPE) Modified PPE: Modified polyphenylene ether (having a structure shown in formula (19), in which R 15 is a methyl group, Y is a dimethylmethylene group (represented by formula (16), R 44 and R 45 A modified polyphenylene ether compound in which the methyl group is a methyl group, SA9000 manufactured by SABIC Innovative Plastics, intrinsic viscosity (IV) in methylene chloride at 25°C of 0.085 dl / g, weight average molecular weight Mw2000, and number of terminal functional groups of 1.8 (others) Epoxy compound: dicyclopentadiene epoxy resin (HP-7200 manufactured by DIC Corporation) Phenol novolac resin: Phenol novolac resin (TD2131 manufactured by DIC Corporation) (Initiator) PBP: α,α'-di(t-butylperoxy)diisopropylbenzene (Perbutyl P (PBP) manufactured by NOF Corporation) (catalyst) Imidazole compound: 2-ethyl-4-methylimidazole (2E4MZ from Shikoku Chemical Industry Co., Ltd.) (Flame retardant) Flame retardant: SAYTEX 8010 by Albemarle (filling material) Silica 1: Vinylsilane-treated spherical silica (SC2300-SVJ manufactured by Admatechs Co., Ltd.) Silica 2: Epoxy silane-treated spherical silica (SC2500-SEJ manufactured by Admatechs Co., Ltd.)
[0210] [Method for preparing resin composition] Next, a method for preparing the resin composition will be described.
[0211] First, each component other than the initiator was added to toluene in the blending ratio shown in Table 3 below so that the solid content concentration was 60 mass%, and mixed. The mixture was heated to 80°C and stirred at 80°C for 60 minutes. Thereafter, the stirred mixture was cooled to 40°C, and the initiator was added in the blending ratio shown in Table 3 below to obtain a varnish-like curable composition (varnish). The mixture was stirred for 60 minutes to prepare a varnish-like resin composition (varnish).
[0212] [Preparation method of copper clad laminate] Next, the obtained varnish was impregnated into glass cloth, which was then heated and dried at 100 to 170° C. for about 3 to 6 minutes to produce a prepreg. Specifically, the glass cloth was #1078 type L glass manufactured by Asahi Kasei Corporation. At that time, the content of the resin composition (resin content) was adjusted to about 66 mass%.
[0213] Next, two sheets of the manufactured prepregs were stacked together, and the following copper foil shown in Table 3 was placed on both sides to form a pressure body. This was then heated and pressed for 100 minutes under conditions of a temperature of 200°C and a pressure of 3 MPa (megapascals) to produce a copper-clad laminate with copper foil adhered to both sides.
[0214] (copper foil) Copper foil-1: Copper foil whose entire surface was treated with a silane coupling agent having an amino group in the molecule (TLC-V1 manufactured by Nan'a Plastics Co., Ltd., copper foil treated with aminosilane, chromium deposition amount on M side: 1.8 atomic %, ten-point average roughness Rz on M side: 1.3 μm, thickness: 18 μm) Copper foil-2: Copper foil whose entire surface was treated with a silane coupling agent having an amino group in the molecule (FX-WS manufactured by Furukawa Copper Foil Taiwan Co., Ltd., copper foil treated with aminosilane, chromium coverage on M side: 7.4 atomic %, ten-point average roughness Rz on M side: 1.3 μm, thickness: 18 μm) Copper foil-3: Copper foil whose entire surface was treated with a silane coupling agent having an amino group in the molecule (FV-WS (amino) manufactured by Furukawa Electric Co., Ltd., copper foil treated with aminosilane, chromium deposition amount on M side: 7.4 atomic %, ten-point average roughness Rz on M side: 1.3 μm, thickness: 18 μm) Copper foil-4: Copper foil whose entire surface was treated with a silane coupling agent having a vinyl group in the molecule (FV-WS (vinyl) manufactured by Furukawa Electric Co., Ltd., copper foil treated with vinyl silane, chromium coverage on M side: 7.4 atomic %, ten-point average roughness Rz on M side: 1.3 μm, thickness: 18 μm) Copper foil-5: Copper foil whose entire surface was treated with a silane coupling agent having an amino group in the molecule (MLS-G manufactured by Mitsui Mining & Smelting Co., Ltd., copper foil treated with aminosilane, chromium deposition amount on M side: 2.2 atomic %, ten-point average roughness Rz on M side: 2.8 μm, thickness: 18 μm)
[0215] [Chromium and nitrogen element content] The obtained copper-clad laminate was etched for 90 seconds using a cupric chloride solution (liquid temperature 45° C.), and then washed with city water or pure water at room temperature, thereby removing the copper foil.
[0216] The surface elemental analysis was performed by XPS on the surface (exposed surface) of the insulating layer exposed by the etching process. This surface elemental analysis was performed by irradiating the M surface (contact surface) with X-rays under the following conditions from a direction perpendicular to the M surface under vacuum, adjusting the irradiation height to a position where the photoelectrons emitted with the ionization of the sample could be detected with the strongest intensity. For XPS, a PHI 5000 Versaprobe manufactured by ULVAC-PHI Inc. was used, and the measurement was performed under the following conditions. X-rays used: Monochrome Al-Kα rays X-ray beam diameter: approx. 100 μmφ (25 W, 15 kV) Analysis area: approx. 100μmφ
[0217] The values obtained by the above measurement were converted into quantitative values using a relative sensitivity coefficient incorporated in the analysis software provided with the above device.
[0218] As a result, the amount of chromium element and the amount of nitrogen element were measured relative to the total amount of elements measured by XPS.
[0219] [Surface roughness Rz] The surface roughness (ten-point average roughness Rz) of the exposed surface was measured in accordance with JIS B 0601:1994 using a surface roughness and shape measuring instrument (SURFCOM500DX) manufactured by Tokyo Seimitsu Co., Ltd.
[0220] [evaluation] The copper-clad laminate (evaluation substrate) was evaluated by the following method.
[0221] [Transmission loss] The metal foil (copper foil) on one side of the evaluation board (metal-clad laminate) was processed to form 10 wires with a line width of 100 to 300 μm, a line length of 1000 mm, and a line spacing of 20 mm. A three-layer board was produced by secondarily laminating two sheets of the prepreg and metal foil (copper foil) on the surface of the wiring-formed side of the board on which the wiring was formed. The line width of the wiring was adjusted so that the characteristic impedance of the wiring after the three-layer board was produced was 50 Ω.
[0222] The transmission loss (passage loss) (dB / m) at 12.5 GHz of the wiring formed on the obtained three-layer board was measured using a network analyzer (N5230A manufactured by Keysight Technologies, Inc.).
[0223] [Solder heat resistance] When preparing the evaluation board, a copper-clad laminate was prepared by stacking one prepreg on each side of the copper-clad laminate that had been entirely etched, and heating and pressing the laminate for 100 minutes at a temperature of 200° C. and a pressure of 3 MPa to obtain a copper-clad laminate with copper foil attached to both sides. The copper-clad laminate thus formed was cut into 50 mm×50 mm pieces, and the copper foil on both sides was removed by etching. The evaluation laminate thus obtained was immersed in a solder bath at 288° C. for 30 seconds. The immersed laminate was then visually observed for the presence or absence of blistering. This observation was performed on two laminates. If no blistering was observed (if the number of blistering was 0), the evaluation was made as “◎”. If the number of blistering was 1, the evaluation was made as “◯”, and if the number of blistering was 2, the evaluation was made as “×”.
[0224] [Boiling solder heat resistance 1] A laminate for evaluation was obtained in the same manner as in the evaluation of solder heat resistance described above, and the evaluation laminate was immersed in boiling ion-exchanged water for 4 hours before being immersed in a solder bath at 288° C. for 30 seconds, and the evaluation criteria were the same as in the evaluation of solder heat resistance described above.
[0225] [Boiling solder heat resistance 2] A laminate for evaluation was obtained in the same manner as in the evaluation of solder heat resistance described above, and the evaluation laminate was immersed in boiling ion-exchanged water for 6 hours before being immersed in a solder bath at 288° C. for 30 seconds, and the evaluation criteria were the same as in the evaluation of solder heat resistance described above.
[0226] The results of each of the above evaluations are shown in Table 3. Note that for each copper-clad laminate, a "○" in the copper foil column of Table 3 indicates that the copper foil used was one selected from the group consisting of 1 and 2.
[0227] [Table 3]
[0228] As can be seen from Table 3, in the case of the copper-clad laminate obtained using a copper foil in which the amount of chromium element obtained by XPS measurement on the exposed surface is 7.5 atomic % or less and the surface roughness of the exposed surface is 2.0 μm or less in ten-point average roughness (Examples 1 to 7), the transmission loss was low and the heat resistance was high compared to the case in which the amount of chromium element exceeds 7.5 atomic % (Comparative Examples 1 and 2). In addition, the copper-clad laminates according to Examples 1 to 7 had a low transmission loss compared to the case in which the insulating layer was a resin composition containing an epoxy compound and a phenol novolac compound, not a resin composition containing the modified polyphenylene ether compound (Comparative Example 3). In addition, the copper-clad laminates according to Examples 1 to 7 had a low transmission loss compared to the case in which the surface roughness of the exposed surface exceeds 2.0 μm in ten-point average roughness (Comparative Example 4).
[0229] This application is based on Japanese Patent Application No. 2019-194375, filed on October 25, 2019, the contents of which are incorporated herein by reference.
[0230] In order to express the present invention, the present invention has been described adequately and sufficiently through the embodiments in the above description, but it should be recognized that those skilled in the art can easily modify and / or improve the above-mentioned embodiments. Therefore, unless the modification or improvement made by those skilled in the art is at a level that departs from the scope of the claims described in the claims, the modification or improvement is interpreted as being included in the scope of the claims. [Industrial Applicability]
[0231] According to the present invention, a copper-clad laminate and a resin-coated copper foil are provided that can suitably manufacture a wiring board having a high signal transmission speed and high heat resistance. Also, according to the present invention, a wiring board having a high signal transmission speed and high heat resistance is provided.
Claims
1. A copper clad laminate comprising an insulating layer and a copper foil in contact with at least one surface of the insulating layer, The insulating layer includes a cured product of a resin composition containing a polymer having a structural unit represented by the following formula (1) in a molecule, The copper foil comprises a copper foil base material, and a coating layer disposed on the copper foil base material in the following order: a rust-preventive layer containing chromium; and a silane coupling agent layer formed by treating the copper foil base material with a silane coupling agent having an amino group in its molecule. the anticorrosive layer has a thickness such that the amount of chromium element measured by X-ray photoelectron spectroscopy on an exposed surface of the insulating layer exposed by etching the copper-clad laminate with a cupric chloride solution at a liquid temperature of 45° C. for 90 seconds is 0.1 to 7.5 atomic % relative to the total amount of elements measured by X-ray photoelectron spectroscopy; the silane coupling agent layer has a thickness such that the amount of nitrogen element on the exposed surface as measured by X-ray photoelectron spectroscopy is 0.1 to 5.0 atomic % relative to the total amount of elements as measured by X-ray photoelectron spectroscopy, A copper-clad laminate characterized in that the exposed surface has a surface roughness of 0.2 to 2.0 μm in ten-point average roughness. 【Chemistry 1】 [In formula (1), Z represents an arylene group, R 1 ~R 3 each independently represents a hydrogen atom or an alkyl group; R 4 ~R 6 each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms.
2. 2. The copper-clad laminate according to claim 1, wherein the amount of nitrogen element on the exposed surface measured by X-ray photoelectron spectroscopy is 1.0 to 5.0 atomic % relative to the total amount of elements measured by X-ray photoelectron spectroscopy.
3. The copper-clad laminate according to claim 1 or 2, wherein the structural unit represented by the formula (1) includes a structural unit represented by the following formula (2): 【Chemistry 2】 [In formula (2), R 4 ~R 6 each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms; R 10 represents an arylene group having 6 to 12 carbon atoms.
4. The copper-clad laminate according to claim 3 , wherein the structural unit represented by the formula (2) includes a structural unit represented by the following formula (3): 【Chemistry 3】 [In formula (3), R 4 ~R 6 each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms.
5. The copper-clad laminate according to any one of claims 1 to 4, wherein the polymer further comprises a polymer having a structural unit represented by the following formula (4) in the molecule: 【Chemistry 4】 [In formula (4), R 11 ~R 13 each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms; R 14 represents an aryl group.
6. The copper-clad laminate according to claim 5, wherein the aryl group in the structural unit represented by the formula (4) has an alkyl group having 1 to 6 carbon atoms.
7. The copper-clad laminate according to any one of claims 1 to 6, wherein the weight average molecular weight of the polymer is 1,500 to 40,000.
8. The polymer is represented by the formula (1), and R 1 ~R 3 The copper-clad laminate according to any one of claims 1 to 7, wherein the equivalent weight of the vinyl group contained in the structural unit in which is a hydrogen atom is 250 to 1,200.
9. The copper-clad laminate according to any one of claims 1 to 8, wherein the resin composition further contains a polyphenylene ether compound.
10. A wiring board comprising: wiring formed by partially removing the copper foil provided on the copper-clad laminate according to any one of claims 1 to 9; and the insulating layer.
11. The insulating layer includes a plurality of layers, The wiring board according to claim 10 , wherein the wiring is disposed between the insulating layers.
12. A resin-coated copper foil comprising a resin layer and a copper foil in contact with at least one surface of the resin layer, The resin layer includes a resin composition containing a polymer having a structural unit represented by the following formula (1) in a molecule, or a semi-cured product of the resin composition, The copper foil comprises a copper foil base material, and a coating layer disposed on the copper foil base material in the following order: a rust-preventive layer containing chromium; and a silane coupling agent layer formed by treating the copper foil base material with a silane coupling agent having an amino group in its molecule. the anticorrosive layer has a thickness such that, when the resin layer provided on the resin-coated copper foil is cured, the copper foil in contact with the surface of the cured resin layer is etched for 90 seconds with a cupric chloride solution at a liquid temperature of 45° C. to expose the cured resin layer, and the amount of chromium element measured by X-ray photoelectron spectroscopy on the exposed surface of the cured resin layer is 0.1 to 7.5 atomic % relative to the total amount of elements measured by X-ray photoelectron spectroscopy; the silane coupling agent layer has a thickness such that the amount of nitrogen element on the exposed surface as measured by X-ray photoelectron spectroscopy is 0.1 to 5.0 atomic % relative to the total amount of elements as measured by X-ray photoelectron spectroscopy, The resin-coated copper foil is characterized in that the exposed surface has a surface roughness of 0.2 to 2.0 μm in ten-point average roughness. 【Chemistry 5】 [In formula (1), Z represents an arylene group, R 1 ~R 3 each independently represents a hydrogen atom or an alkyl group; R 4 ~R 6 each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms.
Citation Information
Patent Citations
Curable composition, polymer insulating material, method for producing the same, and substrate
JP2002363232A
Substrate for flexible printed wiring board
JP2003298230A
Printed wiring board, semiconductor package, semiconductor device and printed wiring board manufacturing method
JP2014229775A
Metal-clad laminate and method for producing the same, metal foil with resin and printed wiring board
JP2016028885A
Soluble polyfunctional vinyl aromatic copolymer, method for producing the same, curable resin composition, and cured product of the same
JP2018039995A